Whole-exome sequencing reveals a novel frameshift and a recurrent nonsense SPG11 variant causing rare familial amyotrophic lateral sclerosis type 5 in two consanguineous Pakistani families - Riaz Ahmad; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2026)
Background Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects both upper and lower motor neurons, disturbing communication between the brain and muscles. So far, few reports have been published for the SPG11 -associated ALS, and this is the first documented case from Pakistan. Methods We report a rare subtype of ALS with an autosomal recessive mode of inheritance with juvenile onset before 25 years of age in the five affected individuals from two unrelated families. Whole-exome sequencing was performed to identify disease-causing variants, and selected variants were further prioritized based on predicted pathogenicity and similarity to clinical phenotypes. Results Two homozygous variants within the SPG11 gene were identified as pathogenic according to the ACMG and ClinGen Sequence Variant Interpretation (SVI) Working Group recommendations: a novel truncation (NM_025137.4:c.6738dup, p.Glu2247Ter) variant as validated by Sanger sequencing and a recurrent nonsense (NM_025137.4: c.782C>A, p.Ser261Ter) variant (rs765477482) previously reported in a family affected with autosomal recessive hereditary spastic paraplegia (ARHSP). In silico prediction tools further confirmed their pathogenicity. Conclusion Five patients with juvenile-onset ALS born to consanguineous parents were found to have homozygous SPG11 gene variants. Our findings describe the overlapping phenotypes of SPG11 -related autosomal recessive juvenile ALS and ARHSP, suggesting that these disorders show a clear overlapping phenotype with common genetic defects. In clinical practice, it is challenging to distinguish between these two disorders. Additional Mendelian cases should be included to clarify further and investigate whether these represent two diverse diseases caused by variants in a single gene.

Clinico-genetic heterogeneity in Pakistani families affected with muscular dystrophies - Riaz Ahmad; Muhammad Almas Hashmi; Asad Ullah; Ubaid Ur Rehman; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2026)
Background Muscular dystrophies are a group of inherited neuromuscular disorders characterized by degenerative and progressive muscle weakness. Duchenne muscular dystrophy (DMD), Becker muscular dystrophy (BMD) and merosin-deficient congenital muscular dystrophy type 1 (MDC1A) are frequent forms caused by DMD (NM_004006.3) and LAMA2 (NM_000426.4) mutations, respectively. Methods and results Our study used whole exome sequencing to explore the molecular genetics of muscular dystrophies in six unrelated Pakistani families. We found four novel variants in the LAMA2 ; c.7470_7473del; p.(Lys2490AsnfsTer56) in family A, c.7807del; p.(Ala2603HisfsTer4) in family C, c.8651T > C; p.(Met2884Thr) in family D and c.4127T > A; p.(Leu1376Ter) in family E associated with MDC1A in these families. Furthermore, two already cited DMD variants were identified: c.10,801 C > T; p.(Gln872Ter) in family B and hemizygous genomic deletion in DMD (NM_004006.3):g.32438241_32809611del (corresponding to deletion of exons 7–29; GRCh38), which was identified (in family F) associated with BMD and DMD, respectively. Conclusions We present the first report of MDC1A-associated phenotypes caused by the LAMA2 gene in the Pakistani population, while DMD -related cases have already been documented in the literature and public databases. Clinical and molecular diagnosis of these six affected families will be valuable in therapeutic interventions and prenatal diagnosis of neuromuscular dystrophies in the familial and Pakistani populations. Our study emphasizes the effectiveness of next generation sequencing technology over traditional diagnostic methods such as muscle biopsies.

Chitinase-primed ultrasound enhances Saccharomyces cerevisiae cell-wall deconstruction and yeast-protein remodelling in two complementary model systems - Talha Riaz; Xianjiang Ye; Te Yu; Zhijun Xia; Muhammad Moeid Khan; Xuan Yao; Rabiya Riaz; Sadia Ansar; Zhou Chen; Muhammad Atiq Ashraf; Chuanyan Pan; Yongguo Jin; et al. (Food Research International, 2026)

Boron-mediated pectin demethylesterification improves Na+ retention in root cell wall and alleviates salt stress in Brassica napus L. - Yu Yang; Wenjing Hao; Rui Jing; Xiaolei Feng; Diqing Yin; Muhammad Riaz; Mu Lu; Yusheng Niu; Lei Yan (Plant Science, 2026)

Landslide hazard prediction in data-scarce mountainous region using satellite-based frequentist rainfall thresholds - Muhammad Tayyib Riaz; Muhammad Basharat; Maria Teresa Brunetti; Massimo Melillo; Adnanul Rehman; Ming Peng (Engineering Geology, 2026)

Advances in antimicrobial biomaterials for food packaging: A focus on food safety mechanisms and applications - Ahsan Riaz Khan; Navdeep Singh Grewal; Dur E. Sameen; Farah Khan; Rana Muhammad Zulqarnain; Hai-Jun Zhang (Food Chemistry, 2026)

Adaptation of wild-type rabies virus on vaccine producing cell line and its quantification by peroxidase-based immunostaining - Muhammad Rehan Riaz; Syed Muhammad Kamran Ullah; Muhammad Rashid; Kaleem Ullah; Hamid Ahmad; Qari Muhammad Kaleem; Faiza Jamil; Saifullah Khan (Archives of Virology, 2026)

Long-Term Fermented Chicken Manure (CM) Amendment Enhances Soil Health, Sugar Beet Yield, and Shifts Microbial Functional Diversity - Jianyu Zhang; Songlin Yang; Xiaochen Lin; Shafaque Sehar; Muhammad Ishfaq; Muhammad Riaz; Muhammad Faheem Adil; Saqib Bilal; Xiaoyu Zhao; Jean Wan Hong Yong; Baiquan Song (Sugar Tech, 2026)

Revisiting iron nutrition: a nano–organic approach for enhanced wheat yield, antioxidant resilience, and photosynthetic pigments - Hafiz Muhammad Jhanzab; Farhat Yasmeen; Ayshah Aysh Alrashidi; Muhammad Tanveer Altaf; Riaz Ahmad; Mohamed Ebaid; Ammar AL-Farga (Cereal Research Communications, 2026)

Integrating machine learning and LOPCOW-CRADIS framework for optimizing air quality index and urban clean environment using intuitionistic fuzzy credibility numbers - Iqra Zareef; Muhammad Riaz (Environment, Development and Sustainability, 2026)

Heterojunction interfacial Mo − S bond induced directional electron transport enables efficient visible-light-driven hydrogen evolution - Yidong Pan; Yufeng Fan; Yang Fu; Zhichao Deng; Muhammad Sohail Riaz; Hong Li; Weiju Hao; Jinchen Fan; Guisheng Li; Qingyuan Bi (Chemical Engineering Journal, 2026)

Propylparaben exposure induces hematobiochemical alterations, genotoxicity oxidative stress and apoptosis in Labeo rohita - Hasnain Akmal; Shabbir Ahmad; Muhammad Ahsan Riaz; Farhat Jabeen; Shahid Sherzada; Khurram Shahzad (Veterinary Research Communications, 2026)

Nano-enabled RNAi strategies for sustainable citrus protection against viral pathogens - Amjad Ali; Ameel Riaz; Muhammad Faiq; Jaya Seelan Sathiya Seelan; Faheem Shehzad Baloch; Muhammad Aasim; Muhammad Shahbaz (Planta, 2026)

Molecular mechanisms underlaying fluoride-induced neurotoxicity: interplay of antioxidants and endoplasmic reticulum stress–mediated apoptotic pathways in rats - Ashiru Dahiru; Ismat Nawaz; Syeda Kiran Riaz; Summaya Sohail Chaudry; Muhammad Jadoon Khan; Qingyu Huang; Muhammad Abbas; Syed Ali Musstjab Akber Shah Eqani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Investigating Charge-Carrier Dynamics in Heteroatom-Functionalized Triphenylamine Hole Transport Materials for Perovskite Solar Cells - Faiza Iram; Zobia Irshad; Riaz Hussain; Muhammad Imran; Mahmood Ahmed; Muhammad Adnan; Jae Kwan Lee (Journal of Fluorescence, 2026)

Transforming Banana Peel Waste into a Nano Biostimulant: Effects on Maize Seed Germination and Physio-Morphological Traits - Palwasha Sajjad; Umair Riaz; Azer Ahmadov; Tanveer-ul-Haq; Nazar Fareid; Faiza Hassan; Muhammad Adeel; Ayta Umar; Ren Maozhi; Muhammad Usman Aslam; Lamy Hamed (Journal of Plant Growth Regulation, 2026)

Antimicrobial Plant Protein Patatin: Identification and In-Silico Analysis Through Phylogenetics and Molecular Docking - Sarah Tariq; Binish Khaliq; Hina Shaheen; Ahmad Riaz; Sumaira Rubbani; Muhammad Sajid Hamid Akash; Amjad Hussain; Muhammad Imran; Muhammad Arslan Javed; Ahmed Akrem; Sohaib Mehmood; Sajjad Azam (Agricultural Research, 2026)

Fintech-driven sustainability: Examining the pathways to sustainable performance through innovation and circular practices in emerging market SMEs - Muhammad Waqar; Adil Riaz; Jibal Baig; Zahid Bashir; Zhonghua Cai (Journal of Cleaner Production, 2026)

Integrative screening of cotton genotypes against salt stress using pre-breeding and machine learning methods - Zunaira Anwar; Sajid Shokat; Allah Ditta; Muhammad Kashif Riaz Khan (Biocatalysis and Agricultural Biotechnology, 2026)

Chinese milk vetch as green manure enables simultaneous NPK fertilizer reduction while enhancing rice yield and soil fertility in subtropical systems - Tahir Shah; Muhammad Sufhan Tahir; Adnan Anwar Khan; Muhammad Fraz Ali; Sadam Khan; Muhammad Riaz; Yajun Gao; Qiang Zhu (Applied Soil Ecology, 2026)

Impact of insect pollinators on the yield and quality of cucumber (Cucumis sativus L.) - Muhammad Mamoon-ur-Rashid; Farheen Sayyam; Habib Ali; Modhi O. Alotaibi; Ammara Riaz; Xu Danping; Muhammad Umair Sardar; Aftab Ahmad; Zhuo Zhihang (International Journal of Tropical Insect Science, 2026)

Advancements in Wheat Rust Resistance through Molecular and Field-Based Approaches - Muhammad Waheed Riaz; Dehua Wang; Shams ur Rehman; Yufeng Zhang; Faheem Tariq; Alam Sher; Shabbir Hussain; Muhammad Aamir Manzoor; Abdul Raziq; Zhiying Deng (Journal of Soil Science and Plant Nutrition, 2026)

Antibacterial flavonoid derivatives: in silico ADMET, DFT, Molecular Docking, MD Simulation and in vitro verification - Atif Ishfaq; Affifa Tajammal; Riaz Maira; Aisha Waheed Qureshi; Babar Aleeza; Muhammad Asim Raza Basra (In Silico Pharmacology, 2026)

Protective effects of zinc and Prunus amygdalus against cadmium-induced nephrotoxicity in male Albino rats - Muhammad Talha Ishaq; Faiza Zubair; Naila Riaz; Hira Kanwal; Ayesha Tehreem Shahbaz; Tooba Tahir; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Journal of Trace Elements in Medicine and Biology, 2026)

Next-generation thermal management systems for lithium-ion batteries: Enhancing the performance and safety in electric vehicles - Zahid Bashir; Riaz Hussain; Hafeez Khoharo; Jarrar Ali Jaffri; A.L. Saroj; Shahid Bashir; Jeyraj Selvaraj; Muhammad Shakeel Ahmad (Journal of Environmental Chemical Engineering, 2026)

Retraction notice to “Assessment of hepatotoxicity and nephrotoxicity in Cirrhinus mrigala induced by trypan blue - an azo dye” [Environ. Res. 215 (2022) 114120] - Bilal Hussain; Muhammad Sajad; Hassan Usman; Khalid A. Al-Ghanim; Mian Nadeem Riaz; Aydin Berenjian; Shahid Mahboob; Pau Loke Show (Environmental Research, 2026)

Efficacy of Probiotic Supplementation in Broilers Challenged with Coccidiosis: A Meta-Analysis - Roshan Riaz; Neslihan Ölmez; Ali Raza; Muhammad Shazaib Ramay; Benian Yılmaz; Mükremin Ölmez; Beenish Imtiaz; Hafiz Muhammad Nouman (Probiotics and Antimicrobial Proteins, 2026)

Unlocking the Hydrocarbon Potential of the Canterbury Basin, New Zealand: Geochemical and Basin Modeling Insights for Hydrocarbon Exploration - Muhammad Ubaid Umar; Shenghe Wu; S. M. Talha Qadri; Shafqat Hussain; Khaled Albriki; Muhammad Riaz (Natural Resources Research, 2026)

Anti-inflammatory role of metal and metal oxide nanoparticles: a review of toxicity, green synthesis, and immunomodulatory mechanisms - Rimsha Ashraf; Shaukat Ali; Muhammad Summer; Saima Riaz; Amina Iqbal; Ramzana Bibi; Haiqa Shabbir (Inflammopharmacology, 2026)

Genetic dissection on polyphenol oxidase activity and yellow pigment content in wheat grains during different development stages - Yingxin Guo; Dehua Wang; Qianqian Lv; Xiaojie Yang; Guanying Wang; Muhammad Waheed Riaz; Xin Guo; Jichun Tian; Zhiying Deng (Euphytica, 2026)

Appropriate selection of objective functions with constraints for successive multicycle optimization of the HPR1000 reactor core using deep learning enhanced multi-objective genetic algorithm - Muhammad Kamran Butt; Samia Nasir; Muhammad Ahmad; Muhammad Talha Bin Humayun; Ahmer Riaz; Chenghui Wan; Liangzhi Cao (Annals of Nuclear Energy, 2026)

Biochar application enhances tolerance to boron toxicity in rice (Oryza sativa) seedlings - Muhammad Riaz; Lei Yan; Xia Hao (Soil and Tillage Research, 2026)

Processing sequence as a design lever: pectin pre-complexation enhances ultrasound-driven interfacial loading, functionality, and volatile profile of yeast protein - Talha Riaz; Yuan Ma; Zhijun Xia; Muhammad Moeid Khan; Xianjiang Ye; Muhammad Atiq Ashraf; Rabiya Riaz; Xing Fu; Yongguo Jin (Food Research International, 2026)

A Meta-analysis on the Effects of Postbiotics on Growth Performance and Gut Morphology in Broiler Chickens - Roshan Riaz; Hafz Muhammad Nouman (Probiotics and Antimicrobial Proteins, 2026)

Valorization of recycled concrete fine aggregates in gypsum mortars for developing eco-friendly false ceiling plates - Rashid Latif; Muhammad Rizwan Riaz; Anam Fatima; Rizwan Azam; Muhammad Hassan Javed (Innovative Infrastructure Solutions, 2026)

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Chaotic transitions and multistable regimes in a nonlinear wave model through hybrid analytical–numerical techniques - Muhammad Iqbal; Syeda Sarwat Kazmi; Muhammad Bilal Riaz; Muhammad Aziz Rehman (Modeling Earth Systems and Environment, 2026)
The modified Zakharov–Kuznetsov (mZK) model is a fundamental framework for describing nonlinear phenomena in plasma oscillations, optical systems, discrete electrical lattices, and oceanic wave dynamics. In this work, we establish a unified framework that combines exact solution construction with dynamical systems analysis of the mZK equation. Using the modified Khater method and the Sardar subequation technique under a traveling wave transformation, we derive new and more general families of solitary traveling wave solutions, including trigonometric, hyperbolic, rational, exponential–rational, and complex soliton forms. We show how free parameters govern the existence, shape, and stability of these solutions, with two- and three-dimensional MATLAB simulations illustrating their structures. Furthermore, we reformulate the mZK equation as a planar dynamical system and classify its qualitative features through phase portraits, identifying centers, saddles, and cusps. With the inclusion of periodic external forcing, the reduced system displays bifurcation and chaos, following a period-doubling route with multistability and sensitivity to parameter variations. To the best of our knowledge, this is the first study that simultaneously delivers exact soliton solutions and a complete nonlinear dynamics characterization of the mZK equation. This integrated approach provides a novel template for investigating broader classes of nonlinear evolution equations.

Integrated physicomechanical, petrographic, and geochemical evaluation of eocene carbonate aggregates from the Salt Range, Pakistan - Khawaja Shoaib Ahmed; Muhammad Basharat; Amir Shahzad; Yasir Sirfraz; Muhammad Tayyib Riaz; Usama Shabir Abbasi; Salman Rasheed (Innovative Infrastructure Solutions, 2026)

Retraction Note: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Molecular Identification and Phylogenetic Analysis of Lumpy Skin Disease Virus-P32 Gene in Cattle of Potohar Region, Pakistan - Gohar Khadim; Aamer Ali Shah; Aayesha Riaz; Mian Muhammad Awais; Arfan Yousaf; Mahwish Ali; Bakhtawar Khadim; Nimra Riaz (Current Microbiology, 2026)

Advances in fulvic acid extraction from lignite: techniques, challenges, and applications - Iqra Yousaf; Lizhen Gao; Iffat Riaz; Sidra Pervaiz; Muhammad Usman (Environmental Monitoring and Assessment, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Potential Application of NADPH-Dependent FMN Reductase-Harboring Delftia Acidovorans in Laboratory-Scale Textile Wastewater Treatment and Re-Use - Awais Maqsood; Syeda Khola Tazeen; Sabir Hussain; Faisal Mahmood; Sher Muhammad; Muhammad Shafiq Shahid; Faizah Amer Altihani; Mohamed Hashem; Danish Riaz; Irfan Manzoor; Muhammad Shahid (Water, Air, & Soil Pollution, 2026)

Wetland Transformation and Waterfowl Decline: Linking Habitat Change to Northern Pintail Losses in Punjab - Nayyar Batool; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Misbah Sarwar; Javaria Ikram; Naima Huma Naveed; Iram Inayat; Shaheen Riaz; Hakim Bibi (Environmental Management, 2026)

Environmental persistent free radicals mediated reactive oxygen species generation and oxidative stress responses in soil microbial communities: A review - Sadam Khan; Muhammad Riaz; Shoaib Akhtar; Yuanren Jiang; Chenghe Yan; Kecheng Zhu; Hanzhong Jia (Applied Soil Ecology, 2026)

Agricultural and socio-ecological benefits of reducing chemical nitrogen fertilizer and using organic amendments: a sugar beet case study in China's black soil region - Yunlong Guo; Xiaochen Lin; Muhammad Faheem Adil; Muhammad Ishfaq; Muhammad Riaz; Shafaque Sehar; Songlin Yang; Yan Wang; Zhishan Yan; Baiquan Song (Applied Soil Ecology, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

Potential efficacy of insecticides and plant growth regulators against Oxycarenus hyalinipennis (Costa) during the fruiting stage of cotton (Gossypium hirsutum L.) - Muhammad Saqib Ajmal; Muhammad Farhan; Sajjad Ali; Qaiser Shakeel; Habib Ali; Ammara Riaz; Javaid Iqbal; Konul Ahmadova; Muhammad Sarmad; Muhammad Sajjad (International Journal of Tropical Insect Science, 2026)

Betaine-loaded Foeniculum vulgare@Fe-MOF: A novel approach to combat bleomycin-induced hepatotoxicity in rats - Sana Batool; Iftikhar Ahmed; Calvyn Howells; Li Haitao; Muhammad Saqib Saif; Tuba Tariq; Riaz Hussain; Muhammad Mahmood Ahmad; Sobia Tauheed; Chaokun Hong; Tauseef Munawar; Shahbaz Gul Hassan; et al. (Journal of Environmental Chemical Engineering, 2026)

Nigella sativa L. (Black cumin) seeds impart protective effects against Staphylococcus aureus induced septic arthritis through the modulation of immune and inflammatory responses - Muhammad Aamir Shaheen; Adeel Sattar; Huma Rao; Amjad Riaz; Abdul Basit (Food Bioscience, 2026)

Numerical analysis of Williamson nanofluid flow past an oscillating vertical porous plate: influence of Soret, Dufour, and chemical reaction effects - Albara Alrawashdeh; Muhammad Awais; Hakim Al Garalleh; Raja Farrukh Riaz (Modeling Earth Systems and Environment, 2026)

Management of canola aphids (Hemiptera: Aphididae) using potassium silicate (K2SiO3) in integration with Chrysoperla carnea Stephens - Dilawar Abbas; Umer Liaqat; Habib Ali; Tehniyat Fatima; Ammara Riaz; Inzamam Ul Haq; Zahid Mahmood Sarwar; Muhammad Abaid Ullah; Muhammad Adeel Ghafar; Kamran Haider; Muhammad Lubaid Khalid; Modhi O. Alotaibi; et al. (Journal of Plant Diseases and Protection, 2026)

Precision Rewiring of Stress-Responsive Gene Networks Via CRISPR: Mechanistic Pathways Toward Climate-Smart Agriculture - Burhan Khalid; Muhammad Umer Javed; Muhammad Ikram; Muhammad Ateeq; Muhammad Atiq Ashraf; Talha Riaz; Shumaila Nawaz; Rizwan Maqbool (Journal of Crop Health, 2026)

Formulation and characterization of escin loaded-chitosan nanoparticles and assessment of its anti-arthritic potential in Wistar rats: a mechanistic approach - Ayesha Riaz; Ammara Saleem; Muhammad Furqan Akhtar (Inflammopharmacology, 2026)

Continuous biochar application ameliorates saline-alkali soils: Effects on soil multifunctionality, salt redistribution, microbial dynamics, and cotton productivity over two years - Xiangling Wang; Xiaoyang Xia; Muhammad Riaz; Jiyuan Wang; Cuncang Jiang (Applied Soil Ecology, 2026)

Evaluation of resistance level of exotic cotton Gossypium hirsutum accession “Mac-07” against cotton leaf curl disease complex - Khalid Pervaiz Akhtar; Sajawal Iqbal; Najeeb Ullah; Muhammad Qasim Aslam; Muhammad Kashif Riaz Khan; Imran Amin (Journal of Plant Pathology, 2026)

Antihyperlipidemic activity of Kalanchoe blossfeldiana leaf extract: phytochemical, in vitro, in vivo, and in silico insights - Abdul Rehman Riaz; Muhammad Islam; Hamid Saeed (In Silico Pharmacology, 2026)

Water resource management optimization model for decision analytics using complex q-rung picture fuzzy information and yager power operators - Subramanian Petchimuthu; Fathima Banu M; Muhammad Riaz; Dragan Pamucar (Environment, Development and Sustainability, 2026)

Ecological Insights into Plant Diversity and Distribution Along Environmental Gradients in Haveli Kahuta, Pakistan - Syed Tahir Hussain Bukhari; Khawaja Shafique Ahmad; Muhammad Tayyib Riaz; Majid Mahmood Tahir; Ansar Mehmood; Ummar Iqbal; Tajmal Imtiaz; Hazem M. Kalaji; Manzer H. Siddiqui (Environmental Monitoring and Assessment, 2026)

A Snapshot of Brucellosis as an Occupational Health Hazard in Animal Handlers of an Agroecological Zone of Southern Punjab, Pakistan - Abdul Sammad Ali Khan Shirwany; Mian Muhammad Awais; Saad Masood; Aayesha Riaz; Masood Akhtar; Hosny El-Adawy; Faqir Muhammad; Muhammad Irfan Anwar; Mamoona Chaudhry (Journal of Agromedicine, 2026)

Short dry period improves postpartum energy balance and reproduction but reduces milk yield in dairy cows - Melad Ahmed; Amjad Riaz; Nasim Ahmad; Muhammad Naveed ul Haque; Hifz ul Rahman; Muhammad Yaseen; Talha Ashraf; Muhammad Abdullah; Ali Hassan; Ali Husnain (Theriogenology, 2026)

Spillover dynamics between maritime energy transportation and energy-related uncertainty - Adeel Riaz; Shek Ahmed; Tanzila Yeasmin Nilu; Muhammad Shahbaz (Regional Studies in Marine Science, 2026)

Seed Priming with Osmolytes Ameliorates Salinity Tolerance in Maize (Zea mays L.) Through Embryonic Modifications - Paris Riaz; Ansa Asghar; Sana Fatima; Sana Basharat; Zahida Parveen; Mansoor Hameed; Farooq Ahmad; M. Sajid Aqeel Ahmad; Muhammad Ashraf; Faakeha Islam; Syed Mohsan Raza Shah; Qasim Ali (Journal of Plant Growth Regulation, 2026)

Sustainable self-compacting concrete incorporating industrial waste SCMs: a state-of-the-art review on rheology, durability, microstructural and mechanical performance - Muhammad Khuzaima Qureshi; Hilal Khan; Mati Ullah Shah; Zamil Bin Zahid; Saif Ur Rehman; Raja Dilawar Riaz; Muhammad Usman; Junaid Ahmad; In-Ho Kim (Innovative Infrastructure Solutions, 2026)

Integrated assessment of groundwater potential and quality in a seismically active Himalayan city: a case study from Muzaffarabad, Pakistan - Raja Dilawar Sajjad; Abrar Niaz; Ahmer Bilal; Muhammad Tayyib Riaz; Ali Yousaf Khan; Xiwu Luan (Environmental Geochemistry and Health, 2026)

Recombination hotspots and genetic variability in foot-and-mouth disease virus genomes: a comparative genomic and phylogeographic analysis - Shahid Hussain; Zixiao Jiang; Hasnain Israr; Jadoon Khan; Muhammad Nasir Riaz; Ijaz Ali; Chengjun Wu; Pir Tariq Shah (Archives of Virology, 2026)

Cambrian sequence stratigraphy and depositional dynamics: insights from the Xuankong Temple section, Shanxi, China - Muhammad Riaz; Ziliang Liu; Khalid Latif; Changcheng Wang (International Geology Review, 2025)

Fluorescence Interface Engineering of PEDOT: PSS–HTL and BPhen–ETL Layers in Alq₃-Based OLEDs for Biomedical Applications - Ghazi Aman Nowsherwan; Hafiz Muhammad Khubaib; Muhammad Azhar; Saira Riaz; Shahzad Naseem (Journal of Fluorescence, 2025)

Interaction between biochar and nitrogen fertilizer improves nitrogen utilization efficiency, closely connected with rhizosphere microbes involved in nitrogen-cycling - Hao Xia; Jiyuan Wang; Muhammad Riaz; Saba Babar; Xiangling Wang; Xiaoyang Xia; Bohan Yan; Bo Liu; Cuncang Jiang (Soil and Tillage Research, 2025)

Ameliorating CO₂ capture performance of PEI/PES hybrid membranes via integration of zeolitic imidazolate frameworks - Sadia Sagar; Aqib Riaz; Farzana Siddique; Aysha Siddiqa; Mohsin Ali; Mahnoor Asif; Muhammad Waqas Iqbal; Fawad Inam (Journal of Environmental Chemical Engineering, 2025)

Biochar remodeled rhizosphere microbial community structure and function to alleviate sugar beet under fomesafen phytotoxicity - Yunlong Guo; Xiaochen Lin; Baiquan Song; Chuanhe Zhao; Muhammad Riaz; Muhammad Ishfaq (Journal of Environmental Management, 2025)

Retraction notice to “Development of reduced graphene oxide-supported novel hybrid nanomaterials (Bi2WO6@rGO and Cu-WO4@rGO) for green and efficient oxidative desulfurization of model fuel oil for environmental depollution” [Environ. Res., Part A, 212 (2022), 113160] - Aqsa Riaz; Muhammad Saeed; Mamoona Munir; Azeem Intisar; Sabah Haider; Shahzaib Tariq; Nazim Hussain; Rehana Kousar; Muhammad Bilal (Environmental Research, 2025)

Impact of pairing gaps on β-decay properties and stellar electron capture rates - Jameel-Un Nabi; Arslan Mehmood; Muhammad Riaz (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

QARS1 associated developmental epileptic encephalopathy: first report of a rare homozygous missense variant from Pakistan causing nonepileptic phenotype in a family of seven patients and a comprehensive review of the literature - Riaz Ahmad; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2025)
Background Pathogenic variants in QARS1 (MIM:603727; Glutaminyl-TRNA Synthetase 1), which encodes Glutaminyl-tRNA synthetase 1, have been associated with rare progressive microcephaly with seizures and cerebral and cerebellar atrophy (MSCCA MIM:615760). Only a handful of MSCCA patients have been reported in the literature mostly associated with compound heterozygous QARS1 variants. In the current study, we aimed molecular characterization of a large consanguineous Pakistani family affected with microcephaly, severe intellectual and developmental disability. Methods We isolated genomic DNA from blood samples collected from the two affected and three normal individuals of the family. We employed whole exome sequencing, homozygosity mapping, Sanger sequencing and in silico protein modelling tools to characterize the pathogenic variant causing the disease phenotype. Moreover, we collected data of 26 MSCCA patients previously reported in the literature. Results The phenotype in the affected individuals of the family was characterized by microcephaly, severe intellectual and developmental disability, but no epilepsy. We found a rare QARS1 variant NM_005051.3:c.1133G > A, p.(Arg378His) in homozygous state in the family. This variant was recently cited in a patient of Turkish ethnicity, the only MSCCA patient reported with nonepileptic phenotype. This variant lying in the catalytic domain of glutaminyl-tRNA synthetase 1 showed deleterious structure and functional impacts on the protein predicted by in silico tools. The variant was classified as ‘likely pathogenic’ following ACMG guidelines. Conclusions We present first report of QARS1 associated developmental encephalopathy from Pakistan. Our study adds to the restricted clinical and mutational database of this rare disorder supporting the growing evidence that homozygous missense QARS1 genotypes may lead to the milder phenotype. The reports of more patients with molecular studies will enhance the understanding of the genotype-phenotype correlations.

Molecular and computational analysis of a novel pathogenic variant in emopamil-binding protein (EBP) involved in cholesterol biosynthetic pathway causing a rare male EBP disorder with neurologic defects (MEND syndrome) - Hadiba Bibi; Riaz Ahmad; Fatima Rahman; Shazia Maqbool; Muhammad Naeem; Stephanie Efthymiou; Henry Houlden (Molecular Biology Reports, 2025)
Background Male EBP disorder with neurologic defects (MEND syndrome) is an extremely rare disorder with a prevalence of less than 1/1,000,000 individuals worldwide. It is inherited as an X-linked recessive disorder caused by impaired sterol biosynthesis due to nonmosaic hypomorphic EBP variants. MEND syndrome is characterized by variable clinical manifestations including intellectual disability, short stature, scoliosis, digital abnormalities, cataracts, and dermatologic abnormalities. The goal of this study was to investigate the disease-causing variants in a family of two patients affected with MEND syndrome. Methods The genomic DNA of the two patients with MEND syndrome was subjected to whole exome sequencing to identify disease-causing variants. Segregation of the identified variant was tested through Sanger sequencing. Several in-silico tools were used to evaluate the pathogenicity of the variant. Protein’s 3D structure analysis systems were used to predict the impact of the identified variant on the binding and function of the mutated EBP protein including AlphaFold, PyMOL, AutoDock, ChimeraX and Discovery Studio. Results A novel pathogenic missense EBP variant NM_006579.3:c.556T > C (Trp186Arg) was found segregating in the affected family. In-silico analysis and molecular docking results supported the pathogenicity of the identified variant. Conclusion Our study expands the mutation spectrum of EBP and adds to the restricted reports of MEND patients. It strengthens the body of evidence that supports the role of EBP in the MEND syndrome phenotype. To our knowledge, this is the first report of this disorder from Pakistan.

Report of a novel missense TDP1 variant in a Pakistani family affected with an extremely rare disorder congenital spinocerebellar ataxia with axonal neuropathy type 1 (SCAN1) - Riaz Ahmad; Filza Sayyad; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2025)
Background Spinocerebellar ataxia with axonal neuropathy type 1 (OMIM: 607250) is an extremely rare autosomal recessive disorder caused by a mutation in the tyrosyl-DNA phosphodiesterase 1 ( TDP1) gene. Only a single missense variant (p.His493Arg) in this gene has been reported. This variant was found in three Arab families with a possible common founder effect. Methods and Results We report a female patient born to a consanguineous Pakistani family segregating autosomal recessive spinocerebellar ataxia with axonal neuropathy type 1. The patient presents additional clinical features distinct from previously reported Arab families including congenital onset of the disease. We performed whole exome sequencing with the patient’s DNA and identified a novel missense variant (NC_000014.9:g.89991982C > T; p.His478Tyr) in exon 13 of the TDP1 gene. Sanger sequencing was performed to verify the autosomal recessive segregation of the p.His478Tyr variant in the family. Conclusion The current study expands both the clinical and mutation spectrum of the TDP1 associated spinocerebellar ataxia with axonal neuropathy type 1 and increases the body of evidence that supports the pathogenic role of TDP1 in cerebellar ataxias with peripheral neuropathy.

Computational identification of membrane proteins for vaccine design against drug-resistant Moraxella catarrhalis - Fizza Arshad; Rania Pervaiz; Asifa Sarfraz; Hasan Ejaz; Amal Alotaibi; Riaz Ullah; Umar Nishan; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2025)

Dynamical transitions and multistability in nonlinear wave systems: dual analytical insights into the geophysical Korteweg–de Vries Equation - Muhammad Iqbal; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman; Mohie M. Alqezweeni (Modeling Earth Systems and Environment, 2025)

Mechanical characterization and impact resistance of concrete incorporating recycled thin-walled hollow tubular GFRP sections - Muhammad Rizwan Riaz; Muhammad Moeed Azhar; Muhammad Fahad Ejaz; Rizwan Azam; Muhammad Faraz Javaid (Innovative Infrastructure Solutions, 2025)

The impact of germination time on nutritional and antioxidant properties of selected cereals - Fahid Nazir; Hamza Zahid; Muhammad Riaz; Yahya Mushtaq; Natasha Amjad; Humaira Iqbal; Muhammad Rizwan Majeed; Shazia Kousar; Muhammad Ahmad Mudassir (Cereal Research Communications, 2025)

Salinity‐induced variations in growth performance, stress biomarkers and biochemical profiles of striped catfish ( Pangasianodon hypophthalmus , Sauvage, 1878) - Muhammad Nouman Riaz; Muhammad Hafeez‐ur‐Rehman; Hamda Azmat; Shahid Mehmood (Journal of Fish Biology, 2025)
Environmental salinity affects the growth, survival rate and physiological functions of fish. In this study, the effects of salinity stress on Pangasianodon hypophthalmus (Sauvage, 1878) fingerlings were examined over a 90‐day period. After acclimatization, a total of 300 P. hypophthalmus fingerlings were randomly assigned into three replicates and divided into five treatment groups with salinity levels of 0‰, 6‰, 12‰, 18‰, and 24‰ and with a stocking density of 20 fish per aquarium. After 90 days, the final weight, weight gain, weight gain percentage and specific growth rate significantly ( p p p p p p p p p p P. hypophthalmus in inland saline groundwater is 12‰, which ensures the maximum survival rate.

Pathogenicity of the Entomopathogenic Fungus Metarhizium anisopliae s.l. (Ascomycota: Hypocreales) Against Sweetpotato Weevil (Cylas formicarius, Coleoptera: Brentidae) Under In Vitro Conditions - Muhammad Riaz; Tsui-Ying Chang; Lekhnath Kafle; Wen-Hua Chen (Neotropical Entomology, 2025)

Environmental extremes in cholistan rangeland ecosystem: effects on floral diversity, rangeland productivity, and carrying capacity - Muhammad Abid; Muhammad Rafay; Muneeb Khalid; Muhammad Umair Riaz (Brazilian Journal of Botany, 2025)

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

Water level forecasting in coastal cities using a hybrid deep learning approach - Abdur Rahman; M. Hafidz Omar; Tahir Mahmood; Nasir Abbas; Muhammad Riaz; Naeem Ramzan (Science of The Total Environment, 2025)

Assessing Heavy Metal Contamination and Health Risks in Urban Street Dust: Insights from Pakistan's Industrial Growth - Ahsan Riaz Khan; Adil Mihoub; Aftab Jamal; Muhammad Farhan Saeed; Somayeh Soltani-Gerdefaramarzi; Muhammad Irfan Ahamad (Water, Air, & Soil Pollution, 2025)

Impact of in-ovo dichromatic lights on embryonic growth, hatching performance and welfare traits in commercial layers - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Saima; Hai Lin (Tropical Animal Health and Production, 2025)

Iron-modified biochar alleviates salt-alkali stress in cotton by enhancing iron availability and rhizosphere microbiome-metabolite interactions - Jiyuan Wang; Muhammad Riaz; Saba Babar; Xiangling Wang; Xiaoyang Xia; Bohan Yan; Cuncang Jiang (Plant and Soil, 2025)

Analyzing the double-chain deoxyribonucleic acid model: bifurcation, chaos, and sensitivity insights through advanced analytical techniques - Sadique Rehman; Aamir Farooq; H. W. A. Riaz; Kamran Ullah Khan; Majid Hussain Shah; Muhammad Ramzan (Theory in Biosciences, 2025)

Spatio-temporal variability study of Shigar Basin Glaciers, Central Karakoram Region, Pakistan - Salman Mustafa; Faisal Rehman; Adnan Shafiq Rana; Tahir Azeem; Omar Riaz; Muhammad Fahad Ullah; Jamil Siddique; Faisal Rehman (Environmental Monitoring and Assessment, 2025)

Distinct gonadotropin receptor profiles across follicle sizes reveal potential mechanism for follicular co-dominance in goats - Waqas Ahmad; Muhammad Suleman; Jawad Akhtar; Amjad Riaz; Khalid Javed; Muhammad Imran Rashid; Muhammad Irfan-ur-Rehman Khan (Theriogenology, 2025)

Insight into amelioration effect of iron-modified biochar on saline-alkali soil chemical properties and bacterial communities along a soil depth gradient - Jiyuan WANG; Riaz MUHAMMAD; Saba BABAR; Zeinab El-DESOUKI; Yuxuan LI; Xiangling WANG; Xiaoyang XIA; Cuncang JIANG (Pedosphere, 2025)

Remarkable energy storage performance in lead-free tungsten bronze ferroelectrics for high temperature applications - Muhammad Fahad Riaz; Fayaz Hussain; Ali Dad Chandio; Zeshan Javed; Wenfeng Yue; Zhenhao Fan; Yuxiao Du; Bingsen Wang; Mohammad Abu Abdeen; Gulmurza Abdurakhmanov; Adil Alshoaibi; Yasemin Tabak; et al. (Chemical Engineering Journal, 2025)

Monochalcogenide-based retina-inspired photosynapses for energy-efficient neuromorphic computing and artificial visual system application - Muhammad Riaz; Zeesham Abbas; Jiayi Li; Syed Khizar Abbas Abidi; Muhammad Hussain; Syed Hassan Abbas Jaffery; Muhammad Suleman; Haider Abbas; Diing Shenp Ang; Sajjad Hussain; Jongwan Jung (Chemical Engineering Journal, 2025)

Integration of Clay and Cytokinin Improves Wheat Yield by Restricting Nickel Uptake and Mobility in Sandy Soil - Muhammad Farooq; Muhammad Riaz; Birhanu Iticha; Zaffar Malik; Aasma Parveen; Muhammad Rizwan; Muhammad Kamran (Water, Air, & Soil Pollution, 2025)

Mechanistic insights into lead uptake and immobilization mediated by soybean biochar and arbuscular mycorrhizal fungi in Bidens parviflora - Sadam Khan; Irfan Ullah Shah Syed; Muhammad Riaz; Muhammad Tariq; Tahir shah; Sidra Sohail; Muhammad Imtiaz; Shoaib Akhtar; Jiang Yuanren; Munib Ahmad; Yurong Yang; Hanzhong Jia (Applied Soil Ecology, 2025)

Recent advances in layered double hydroixdes@MXene (LDHs@MXene) composites: Synthesis, properties, and catalytic applications - Sundas Riaz; Sami Ullah; Sanam Bashir; Aziz ur Rehman; Rashid Iqbal; Tayyaba Najam; Mostafa A. Ismail; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Applied Clay Science, 2025)

Varietal and Geographic Influences on Fruit Quality Traits of Pomegranate (Punica granatum L.) - Muhammad Umair; Ishtiaq Ahmad Rajwana; Kashif Razzaq; Sami Ullah; Umair Riaz; Rashid Iqbal; Saltanat Aghayeva; Maximilian Lackner (Applied Fruit Science, 2025)

Variation in Ectotherm Thermal Tolerances With Elevation and Temperature Across Biological Scales - Imran Khaliq; Edward Lavender; Haseeb Kamran; Muhammad Junaid Shahid; Muhammad Sheraz; Muhammad Awais; Mehtab Shabir; Muhammad Yasir; Abdul Hameed; Muhammad Asgher; Abdul Rehman; Maria Riaz; et al. (Global Ecology and Biogeography, 2025)
Aim Variation in thermal tolerances along environmental gradients is assumed to follow similar patterns across different biological scales, including within and between species, and across communities. However, this assumption has yet to be tested using comprehensive datasets collected through standardised methodologies. Location Southern Asia. Time Period 2017–2019. Major Taxa Studied Ants, beetles, grasshoppers, and spiders. Methods We quantified the associations between thermal tolerance traits and elevation or temperature at three biological scales (community, broad taxonomic group, and species) along two distinct elevational transects in Southern Asia. In total, we measured thermal tolerances of over 15,000 individuals from 114 arthropod species belonging to four invertebrate taxa (ants, beetles, grasshoppers, and spiders). We compared the relationships at each scale using mixed‐effects models. Results At the community scale, across all individuals of all species, we found a consistent decline in the values of three thermal tolerance traits (upper tolerance, lower tolerance, and tolerance breadth) with elevation along the Himalayan transect but an increase in the values of upper and lower tolerance along the Sulaiman transect. The relationships of thermal tolerance traits and elevation/temperature varied among the groups and species between the Himalayan and Sulaiman transects. This suggests that factors beyond elevation, including vegetation composition, microclimate, landscape features, and local adaptation, drive observed variation in thermal tolerance traits among and within species. Conclusion Our study highlights the interplay between thermal physiology and the environment across different habitats and biological scales. Our findings indicate that predicting biodiversity responses to environmental change based on thermal tolerance–environment relationships requires careful consideration of group‐ and species‐level variation. This is essential for improving the accuracy of climate change impact assessments on biodiversity.

Enhanced Photocatalytic Degradation of Methyl Red Dye with Bismuth-Doped ZnO: Kinetics, Mechanistic and Re-cyclability Aspects - Muhammad Alamzeb; Noor-ul-Ain Zulfiqar; Muhammad Faran Akhtar; Iqra Riaz; Faiza Ameen; Aqib Asghar; William N. Setzer (Journal of Fluorescence, 2025)

Evaluation of testicular protective effects of Prunus amygdalus and zinc against cadmium induced toxicity in rats - Ayesha Tehreem Shahbaz; Faiza Zubair; Naila Riaz; Hira Kanwal; Tooba Tahir; Muhammad Talha Ishaq; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Environmental Science and Pollution Research, 2025)

Retraction notice to “Template-based textural modifications of polymeric graphitic carbon nitrides towards waste water treatment” [Chemosphere 302, September 2022,134792] - Umair Azhar; Muhammad Sohail Bashir; Muhammad Babar; Muhammad Arif; Afaq Hassan; Asim Riaz; Rana Mujahid; Muhammad Sagir; Saadat Ullah Khan Suri; Pau Loke Show; Jo-Shu Chang; Kuan Shiong Khoo; et al. (Chemosphere, 2025)

Empowering SMEs with SustainWater Bot to advance urban water sustainability - Muhammad Arslan; Saba Munawar; Zainab Riaz (Sustainable Cities and Society, 2025)

A field study of microbial community differences in rhizosphere vs. non-rhizosphere soil of Chinese cabbage under healthy and clubroot-infected conditions - Jisheng Wang; Sichun Li; Huimiao Yin; Muhammad Riaz; Xinwei Liu; Mengyang Zhang (Rhizosphere, 2025)

Effects of replacement of soybean meal with fermented soybean meal on growth performance, nutrient digestibility and carcass characteristics in broiler - Ali Husnain; Urooj Anwar; Asfa Fatima; Riaz Mustafa; Umar Farooq; Waseem Abbas; Muhammad Farooq Khalid; Muhammad Ashraf; Muhammad Aziz ur Rahman (Livestock Science, 2025)

Epidemiology of Lumpy Skin Disease virus in large ruminants of Potohar region, Pakistan - Gohar Khadim; Aamer A. Shah; Aayesha Riaz; Arfan Yousaf; Mahwish Ali; Mian Muhammad Awais; Muhammad Arif Zafar; Bakhtawar Khadim; Nimra Riaz (Tropical Animal Health and Production, 2025)

Fertilizing Effects of Ulva intestinalis Derived Bio-Stimulant Enhance Spinacea oleracea L. Production, Nutrient Fluxes and Secondary Metabolism Under NaCl Stress - Sadaf Gul; Hamad Aslam; Muhammad Farrakh Nawaz; Ghulam Yasin; Sana Riaz; Maria Hasnain; Mohamed A. El-Sheikh; Emanuele Radicetti; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2025)

Genetic Variability Among Isolates of Curvularia lunata and Exserohilum rostratum Causing Brown Leaf Spot of Rice from Pakistan - Muhammad Faizan Anwar Khan; Abid Riaz; Rafia Ahsan; Ishaq Ahmad; Saif Ullah; Ahmed Raza; Muhammad Zakria (Current Microbiology, 2025)

Host preference and fitness parameters of an invasive leaf eating caterpillar Trilocha varians (Lepidoptera: Bombycidae): implications for ornamental plant pest management - Noura J. Alotaibi; Zhuo Zhihang; Sajida Mushtaq; Sadia Maalik; Muhammad Ramzan; Waqar Majeed; Habib Ali; Xu Danping; Ammara Riaz (International Journal of Tropical Insect Science, 2025)

Identification of a Novel GRM1 Frameshift Variant in Two Pakistani Families Broadens the Genetic Landscape of Ultra-Rare Spinocerebellar Ataxia Type 13 - Riaz Ahmad; Mina Zamani; Eleanor Self; Salah Ud Din Shah; Muhammad Naeem; Henry Houlden (The Cerebellum, 2025)
Autosomal recessive spinocerebellar ataxia 13 (SCAR13) is an extremely rare neurodegenerative disorder characterized by psychomotor delay, ranging from mild to severe intellectual disability with absent or poor speech development, nystagmus and stance ataxia. If ambulation is achieved, affected subjects often exhibit gait ataxia. Additionally, epilepsy and polyneuropathy have been reported in some patients. SCAR13 is caused by pathogenic variants in the GRM1 gene, which is predominantly expressed in the cerebellum, with lower levels in the other parts of the brain. To date, only seven reports of this rare ataxia have been published globally. Our study aimed to investigate clinical and mutation spectrum of GRM1 -associated SCAR13 disorder in nine patients of two consanguineous Pakistani families (designated here to as NP35 and NP36). We performed whole exome sequencing in the probands of the two families followed by Sanger sequencing to test variant segregation. We identified a novel GRM1 frameshift variant (NM_001278064.2):c.3525_3529del; p.(Asn1176IlefsTer71) in both families as a cause of SCAR13. It was classified as a variant of uncertain significance (PM2: pathogenic moderate 2 and PVS1: pathogenic very strong 1) according to the ACMG guidelines. The novel variant exhibited clinical heterogeneity in the two families. Moreover, scoliosis was observed in all four patients of the family NP35, a feature previously documented in only one patient worldwide. Our study expands the limited mutation spectrum of the GRM1 -associated SCAR13. Next-generation sequencing plays a pivotal role in the elucidation of inherited neurological disorders and in a better understanding of the convergent phenotypes.

Correction to: Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2025)

Exploring land subsidence factors with linear Diophantine multi-fuzzy soft information: a hybrid CRITIC-TOPSIS framework - Jeevitha Kannan; Vimala Jayakumar; Muhammad Riaz; Dragan Pamucar; Nithya Sri Shanmugam; Vladimir Simic (Natural Hazards, 2025)

Radon measurements in soils and building materials of Kashmir - Sobia Riaz; Misbah Javed; Muhammad Rashad Khan; Muhammad Khawaja Rafique Mir; Carlo Sabbarese (Isotopes in Environmental and Health Studies, 2025)

Assessing future water scarcity in China under climate and socioeconomic change: Can inter-basin transfers mitigate rising stress? - Muhammad Bilal Idrees; Haixing Liu; Siao Sun; Xian Zhou; Muhammad Zain Bin Riaz (Science of The Total Environment, 2025)

Boron-induced phenylpropanoid metabolism, Na+/K+ homeostasis and antioxidant defense mechanisms in salt-stressed soybean seedlings - Mu Lu; Muhammad Riaz; Kaiqing Tong; Wenjing Hao; Yu Yang; Xiaomeng Zhao; Lu Wang; Yusheng Niu; Lei Yan (Journal of Hazardous Materials, 2025)

Exploitation of Sewage Sludge as a Nutrient-Dense Edaphic Enhancer for Sustainable Agronomy: Assessing Ecological Consequences and Repercussions - Muhammad Riaz; Peng Liu; Muhammad Jamil Khan; Muhammad Tariq; Sadam Khan; Hanzhong Jia (Water, Air, & Soil Pollution, 2025)

Preparation, Characterization and Removal of Acid Blue 129 and Erioglaucine Dyes from Aqueous Solution by Corn Cob Based Activated Carbon - Sultan Alam; Najeeb ur Rahman; Muhammad Ilyas; Iram --; AlSaba Gul; Muhammad Zahoor; Muhammad Naveed Umar; Riaz Ullah; Essam A. Ali (Bulletin of Environmental Contamination and Toxicology, 2025)

Biochar amendment modulate microbial community assembly to mitigate saline-alkaline stress across soil depths - Xiangling Wang; Xiaoyang Xia; Muhammad Riaz; Saba Babar; Zeinab El-Desouki; Muhammad Qasim; Jiyuan Wang; Cuncang Jiang (Journal of Environmental Management, 2025)

Epidemiology and genetic characterization of Alternaria alternata causing leaf spot in Fragaria × ananassa - Nasir Mehmood; Abid Riaz; Salman Ghuffar; Sadaf Anwaar; Nyla Jabeen; Isha Shaheen; Muhammad Qasim; Salma Saeed Khan; Muhammad Rauf; Tauseef Anwar; Huma Qureshi; Ghadah Salim Abusalim; et al. (Fungal Biology, 2025)

Patho-physiological effects of environmental relevant concentrations of lufenuron in male Japanese quails - Silwat Saeed; Gulnaz Afzal; Hafiz Muhammad Ali; Riaz Hussain; Raheela Jabeen; Shumaila Kiran; Rehana Iqbal; Sana Alam; Amna Jalal; Zaib un Nisa; Dalia Fouad; Farid Shokry Ataya; et al. (Environmental Research, 2025)

Decolorization of Dye-Loaded Textile Wastewater: Elucidating the Potential of Chlorella sorokiniana Strain HIN-3 and Effect of Effluent Characteristics - Hadeeqa Arshad; Muhammad Imran; Muhammad Ashraf; Asif Naeem; Muhammad Atif Riaz (Water, Air, & Soil Pollution, 2025)

Insights into the Rhizosphere and Non-Rhizosphere Phosphorus Bioavailability and Plant Responses Under Molybdenum Supply - Muhammad Shoaib Rana; Rui-Long Wang; Muhammad Imran; Yousif Abdelrahman Yousif Abdellah; Muhammad Riaz; Cheng-xiao Hu (Journal of Soil Science and Plant Nutrition, 2025)

Phosphorus-Laden Biochar Mitigates Soil Aluminum Toxicity and Promotes Pakchoi (Brassica chinensis) Growth in Acidic Conditions - Zeinab El-Desouki; Yehia Abouseif; Kesong Lu; Muhammad Riaz; Ali M. Abd-Elkader; Cuncang Jiang (Journal of Soil Science and Plant Nutrition, 2025)

Amendment of Tomato (Lycopersicon esculentum L.) Grown in Calcareous Soil with Spent Mushroom Substrate-derived Biochar: Improvement of Morphological, Biochemical, Qualitative Attributes, and Antioxidant Activities - Hasan Sardar; Muhammad Waqas; Aamir Nawaz; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Ayman A. Ghfar; Saikh M. Wabaidur; Sami Abou Fayssal (Journal of Soil Science and Plant Nutrition, 2025)

Changes in Phosphorus Bioavailability and Bacterial Community Structure Enhance Pakchoi (Brassica Chinensis) Growth Following the Application of Aged Biochar in Acidic Soil - Zeinab El-Desouki; Yehia Abouseif; Muhammad Riaz; Xiangling Wang; Xiaoyang Xia; Jiyuan Wang; Cuncang Jiang (Journal of Soil Science and Plant Nutrition, 2025)

Development and structural performance evaluation of consistent-sized interlocking clay bricks as an alternative to conventional bricks: an experimental investigation - Muhammad Numan; Muhammad Rizwan Riaz; Rizwan Azam; Muhammad Faraz Javaid; Mohamed Zawam (Innovative Infrastructure Solutions, 2025)

Biochar suppresses Clubroot disease in Chinese cabbage by improving soil nutrient conditions and recruiting beneficial microorganisms - Jisheng Wang; Sichun Li; Huimiao Yin; Muhammad Riaz; Xinwei Liu; Mengyang Zhang (Applied Soil Ecology, 2025)

Multifunctional Magnetic Nanoparticles for Targeted Drug Delivery Against Cancer: A Review of Mechanisms, Applications, Consequences, Limitations, and Tailoring Strategies - Shumaila Riaz; Shaukat Ali; Muhammad Summer; Urva Akhtar; Shehzeen Noor; Rimsha Haqqi; Muhammad Adeel Farooq; Iqra Sardar (Annals of Biomedical Engineering, 2025)

Optimizing modified ecological compositions enables eco-friendly control of Tribolium castaneum in grain storage - Muhammad Mohsan; Zahid Mahmood Sarwar; Habib Ali; Inzamam Ul Haq; Ammara Riaz; Rashid Iqbal; Gadah Albasher; Mohammad Javed Ansari (International Journal of Tropical Insect Science, 2025)

Transgenerational Impact of nicotiana tabacum extract on musca domestica (diptera: muscidae) - Muhammad Jamshed Iqbal; Zhihang Zhuo; Inzamam Ul Haq; Yasir Niaz; Basharat Ali; Ammara Riaz; Habib Ali; Rashid Iqbal; Gadah Albasher; Mohammad Javed Ansari (International Journal of Tropical Insect Science, 2025)

Comparative efficacy of Cymbopogon winterianus essential oil and nanoemulsion as a sustainable biopesticide to control Tribolium castaneum: Effect on biomolecules of insect and seed germination - Tanzeela Riaz; Sana Abid; Muhammad Afzal; Farah Rauf Shakoori (Journal of Stored Products Research, 2025)

Occurrence of aflatoxins and effect of preventive practices to inhibit fungal growth and aflatoxin production in leftover flat bread/chapati used as animal feed and stored in Pakistani dairy farms - Mavra Amin; Amir Ismail; Iqra Naeem; Usama Nasir; Muhammad Riaz; Yun Yun Gong; Sher Ali; Michael N. Routledge; Amna Iqbal; Asifa Saif; Carlos Augusto Fernandes Oliveira (Journal of Stored Products Research, 2025)

Carrageenan based edible coating modulates oxidative stress and delays cell wall polysaccharides disassembly in harvested grapefruit - Sajid Ali; Sidra Riaz; Hafiz Umer Javed; Ahmad Sattar Khan; Maratab Ali; Safina Naz; Hasan Sardar; Muhammad Shahzad Saleem (Journal of Stored Products Research, 2025)

Integrated geophysical and hydrogeological techniques for environmental monitoring and assessment: a case study for waste disposal site, Jeddah Saudi, Arabia - Faisal Rehman; Helmy S. O. Abuelnaga; Hussein M. Harbi; Tahir Azeem; Jamil Siddique; Omar Riaz; Muhammad Fahad Ullah; Faisal Rehman (Arabian Journal of Geosciences, 2025)

Impact of End-capped Acceptor Modification in Anthanthrone-Based D-π-A Type Donor Materials for Organic and as Hole Transporting Materials for Perovskite Solar Cells - Nabeel Shahzad; Shahzad Ali Shahid Chatha; Riaz Hussain; Shahid Hussain; Javed Iqbal; Muhammad Adnan (Journal of Fluorescence, 2025)

Iron-modified biochar enhances cotton growth and iron uptake in saline-alkali soil by reducing salinity and facilitating root colonization of beneficial bacteria - Jiyuan Wang; Muhammad Riaz; Saba Babar; Zeinab El-Desouki; Yuxuan Li; Xiangling Wang; Xiaoyang Xia; Cuncang Jiang (Plant and Soil, 2025)

Heavy metal contamination in some commercial marine fishes of Pakistan - Sania Riaz; Muhammad Javed Khan; Iqra Rani; Asad Ali; Muhammad Asghar Qazi; Mehnoor Sameer; Khadija; Nimra Hussain; Shahid Sherzada (Food Additives & Contaminants Part B-Surveillance, 2025)

Learning-based estimation of cattle weight gain and its influencing factors - Muhammad Riaz Hasib Hossain; Rafiqul Islam; Shawn R. McGrath; Md Zahidul Islam; David Lamb (Computers and Electronics in Agriculture, 2025)

Effect of GnRH administration on follicular development and ovulation during the early luteal phase in subtropical goats - Waqas Ahmad; Muhammad Irfan-ur-Rehman Khan; Amjad Riaz; Khalid Javed (Domestic Animal Endocrinology, 2025)

Heavy Metal Uptake by Spirogyra splendida and Spirogyra circumlineata: A Sustainable Approach to Industrial Wastewater Remediation - Sadam Khan; Yuanren Jiang; Siqi Shen; Muhammad Riaz; Muhammad Tariq; Zhenxin Li; Rafiq Ahmad; Sidra Sohail; Nazim Hassan (Water, Air, & Soil Pollution, 2025)

Evaluation of antibody titer and associated risk factors of goat pox vaccine against lumpy skin disease in crossbred buffaloes - Adili Abulaiti; Zahid Naseer; Zulfiqar Ahmed; Shijun Tian; Wenju Liu; Muhammad Shoaib; Asghar Khan; Mohamed Abdelrahman; Faisal Ayub Kiani; Abid Hussain; Aftab Shaukat; Umair Riaz; et al. (Veterinary Research Communications, 2025)

Therapeutic Role of Probiotics Against Environmental-Induced Hepatotoxicity: Mechanisms, Clinical Perspectives, Limitations, and Future - Shehzeen Noor; Shaukat Ali; Muhammad Summer; Anfah Riaz; Laiba Nazakat; Aqsa (Probiotics and Antimicrobial Proteins, 2025)

Investigating the dynamics of (3+1)-dimensional generalized nonlinear physical system via sensitivity and phase portraits - Muhammad Iqbal; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman (Modeling Earth Systems and Environment, 2025)

Exploring chaos and stability: dynamic insights into the stochastic Davey-Stewartson system through advanced sensitivity analysis - Muhammad Moneeb Tariq; Muhammad Bilal Riaz; Tomas Kozubek; Muhammad Aziz-ur-Rehman (Modeling Earth Systems and Environment, 2025)
In this study, we investigate the stochastic Davey-Stewartson equation in the presence of noise. These two-dimensional integrable equations are higher-dimensional versions of the nonlinear Schrödinger equation. Davey-Stewartson equations are important in plasma physics, nonlinear optics, hydrodynamics, and other disciplines because the solutions they provide are valuable in understanding many complex physical phenomena. We employ a modified version of the $$\left( \frac{G'}{G^2} \right)$$ G ′ G 2 approach to handle variable-coefficient systems with imaginary components, such as nonlinear Schrödinger systems. We have discovered a wide range of precise traveling wave solutions, including solitons, kink, periodic, and rational solutions. These solutions may have a significant impact in the domains of engineering and plasma physics. The presented techniques effectively achieve a variety of exponential solutions, including bright, dark, single, rational, and periodic solitary wave solutions. We used MATLAB to simulate our findings and provide 3D, 2D, and counter graphs that illustrate the impact of noise on the precise solutions of the stochastic Davey-Stewartson problem. We apply the Galilean transformation to derive the planar dynamical system, which enhances our understanding of the system’s dynamical analysis. We also conduct a sensitivity analysis to observe the systematic response to various initial conditions. This analysis focuses on the symmetrical aspects of the system and includes the illustration of phase portraits with equilibrium points. We also investigate the chaotic behavior of the planer dynamical system by introducing an additional external force. We predict the system’s behavior to increase the value of intensity and frequency. Our analysis reveals periodic, quasi-periodic, and chaotic processes.

Biological Approaches to Sustainable Management of Fusarium Wilt in Cotton - Iqra Javed; Muhammad Arslan Khan; Hasan Riaz; Shafqat Saeed; Muhammad Sajid; Muhammad Bashair; Zulqarnain Abbas; Haider Ali; Munirah Abdullah Al-Dosary; Muhammad Bilawal Junaid (Journal of Crop Health, 2025)

Harnessing the Power of Plants and Microbes: Strategies to Enhance Crop Performance Under Heat and Salt Stress - Muhammad Riaz; Xiaodong Liu; Fating Yin; Lei Yan (Journal of Crop Health, 2025)

Removal of structurally different textile dyes from water by adsorption onto biomass of non-viable Chlorella sorokiniana strain HIN-3: Kinetics and adsorption isotherms - Hadeeqa Arshad; Muhammad Imran; Muhammad Ashraf; Asif Naeem; Muhammad Atif Riaz (Journal of Applied Phycology, 2025)

Pharmacological modes of plant-derived compounds for targeting inflammation in rheumatoid arthritis: A comprehensive review on immunomodulatory perspective - Laiba Nazakat; Shaukat Ali; Muhammad Summer; Fakiha Nazakat; Shehzeen Noor; Anfah Riaz (Inflammopharmacology, 2025)

Comparative Analysis of Heavy Metals and Minerals in Dairy and Plant-Based Milk Alternatives Available in Pakistan’s Markets - Aiman Usman; Sadaf Yaqoob; Hamza Shafiq; Mamoona Amir; Muhammad Riaz; Kousar Parveen; Usama Usman (Biological Trace Element Research, 2025)

Correction: Assessing municipal solid waste generation, management practices, and health impacts: towards sustainable waste management and environmental protection - Fakhri Alam; Muhammad Salam; Dong Bo; Viola Vambol; Waheed Ullah; Nimra Riaz (Environment, Development and Sustainability, 2025)

Assessing municipal solid waste generation, management practices, and health impacts: towards sustainable waste management and environmental protection - Fakhri Alam; Muhammad Salam; Dong Bo; Viola Vambol; Waheed Ullah; Nimra Riaz (Environment, Development and Sustainability, 2025)

Correction to: Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-Ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

Effect of human chorionic gonadotropin on oocyte maturation and developmental competence in buffalo - Muhammad Bilal; Muhammad Kamran Ashraf; Talha Ashraf; Muhammad Yaseen; Ali Husnain; Muhammad Bilal Bin Majeed; Muhammad Imran; Burhan E. Azam Rana; Muhammad Hassan Mushtaq; Amjad Riaz (Theriogenology, 2025)

Ochrobactrum ciceri and zinc synergy combatting Fusarium verticillioides - Shagufta Perveen; Amna Shoaib; Hafiza Sibgha Yaqoob; Ghanwa Riaz; Muhammad Rafiq (Physiological and Molecular Plant Pathology, 2025)

Paving the path to water security: The role of advanced adsorbents in wastewater treatment - Mushtaq Hussain; Asim Riaz; Hassan Zeb; Awais Ali; Rana Mujahid; Farooq Ahmad; Muhammad Shahzad Zafar (Journal of Water Process Engineering, 2025)

Role of Melatonin in Leaf Gas Exchange by Redox Regulation, K+ Homeostasis and Gene Expression in Canola Under Salinity Stress - Muhammad Ali; Muhammad Farooq; Adnan Noor Shah; Ghulam Hassan Abbasi; Salman Ahmad; Aasma Parveen; Birhanu Iticha; Muhammad Riaz; Muhammad Kamran; Fatima Nisar (Journal of Soil Science and Plant Nutrition, 2025)

RETRACTED ARTICLE: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Physicochemical profiling and health risk evaluation of effluents from textile industries: insights from Faisalabad, Pakistan - Hina Sattar; Muhammad Anwar-ul-Haq; Humera Aziz; Umair Riaz; Ahmad Mahmood; Muhammad Rizwan; Munaza Naseem; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Qasim; Rashid Iqbal (Toxicology and Environmental Health Sciences, 2025)

Peptide-based vaccine design against Hendra virus through immunoinformatics approach - Asifa Sarfraz; Irfa Chaudhary; Fizza Arshad; Muhammad Shehroz; Asia Perveen; Umar Nishan; Abid Ali; Riaz Ullah; Abdelaaty A. Shahat; Aqal Zaman; Mohibullah Shah (Veterinary Immunology and Immunopathology, 2025)

Biohydrogen and biomethane production from biomass gasification: Compositional analysis, recent advancements, challenges, and prospects - Ahmad Naquash; Zeeshan Hameed; Muhammad Abdul Qyyum; Zakir Khan; Ala’a H. Al-Muhtaseb; Amjad Riaz; Moonyong Lee (Process Safety and Environmental Protection, 2025)

Catalytic charge synergy on Ni/Sr@rTiO2 system to promote hydrogen evolution for the implementation of green energy technologies - Ejaz Hussain; Sidra Khan; Muhammad Jalil; Muhammad Zeeshan Abid; Abdul Rauf; Nagina Naveed Riaz; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Impacts of microplastic accumulation in aquatic environment: Physiological, eco-toxicological, immunological, and neurotoxic effects - Eram Rashid; Syed Makhdoom Hussain; Shafaqat Ali; Muhammad Munir; Abdul Ghafoor; Ebru Yilmaz; Mohammed Ali Alshehri; Danish Riaz; Adan Naeem; Eman Naeem (Aquatic Toxicology, 2025)

Chemistry, biosynthesis, and theranostics of antioxidant flavonoids and polyphenolics of genus Rhododendron: an overview - Amjad Hussain; Sajjad Azam; Rabia Maqsood; Riaz Anwar; Muhammad Sajid Hamid Akash; Hidayat Hussain; Daijie Wang; Muhammad Imran; Katarzyna Kotwica-Mojzych; Shoaib Khan; Shabbir Hussain; Muhammad Adnan Ayub (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Unraveling the complexity of solitary waves in the Klein-Fock-Gordon equation: dynamical insights into bifurcation and Chaos analysis - Muhammad Moneeb Tariq; Muhammad Bilal Riaz; Muhammad Aziz ur Rehman; Dilawaiz (Modeling Earth Systems and Environment, 2025)

Optimization-based innovative approach for economical design of reinforced concrete isolated footings - Junaid Waheed; Rizwan Azam; Muhammad Rizwan Riaz; Mansoor Shakeel (Innovative Infrastructure Solutions, 2025)

Computer-aided rational design of a mRNA vaccine against Guanarito mammarenavirus - Mohibullah Shah; Asifa Sarfraz; Muhammad Shehroz; Asia Perveen; Samavia Jaan; Aqal Zaman; Umar Nishan; Arlindo A. Moura; Riaz Ullah; Zafar Iqbal; Mohamed A. Ibrahim (Biotechnology Letters, 2025)

Effects of agricultural plastic films on crop growth and soil health in tobacco fields: A comparative study - Hao Xia; Jia Shen; Muhammad Riaz; Fafen Ran; Tingming Cheng; Xueying Wang; Qing Dong; Chaolong Zu; Bo Liu; Saba Babar; Chaoqiang Jiang (Applied Soil Ecology, 2025)

Human Plasma-Derived Exosomes: A Promising Carrier System for the Delivery of Hydroxyurea to Combat Breast Cancer - Wajeeha Khalid; Afeefa Aslam; Nadeem Ahmed; Muhammad Sarfraz; Jawad Akbar Khan; Sabeeh Mohsin; Muhammad Shahid Riaz Rajoka; Imran Nazir; Muhammad Imran Amirzada (AAPS PharmSciTech, 2025)

Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Iram Ijaz; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

Band Gap Tuning in Mercaptoacetic Acid Capped Mixed Halides Perovskites and Effect of Solvents on Their Fluorescence Dynamics: A Potential Sensor for Polarity - Muhammad Asad Riaz; Usman Zahid; Maria Mukhtar; Muhammad Adnan Khalid; Muhammad Mubeen; Azhar Iqbal (Journal of Fluorescence, 2025)

Global climate change and its impact on the distribution and efficacy of Bacillus thuringiensis as a biopesticide - Muhammad Riaz Ejaz; Samir Jaoua; Niloufar Lorestani; Farzin Shabani (Science of The Total Environment, 2025)

A multi-proxy approach to explore paleoenvironmental oscillations and chronostratigraphy of Thanetian carbonates in Eastern Tethys, Pakistan - Amir Shahzad; Yasir Sirfraz; Khawaja Shoaib Ahmed; Muhammad Hanif; Muhammad Tayyib Riaz; Khawaja Shafique Ahmad; Thierry Adatte (Marine and Petroleum Geology, 2025)

Particle size of wheat straw from genetically improved wheat affects the production performance and feeding behavior of Sahiwal cows - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Muhammad Qamar Bilal; Muhammad Riaz; Muhammad Farooq Khalid; Zia-Ur-Rehman; Urooj Anwar; Riaz Mustafa; Waseem Abbas; Umar Farooq (Tropical Animal Health and Production, 2025)

A systematic investigation of multi-attributive border approximation area comparison approach with Gaussian membership function for optimizing water quality - Yasir Yasin; Gulay Demir; Muhammad Riaz; Muhammad Aslam; Dragan Pamucar (Environment, Development and Sustainability, 2024)

Effect of Arsenic Exposure on AS3MT Protein Levels in Serum of Type 2 Diabetic Patients Compared to Non-diabetics - Saima Shokat; Riffat Iqbal; Muhammad Ahmed Ali; Atif Yaqub; Shaista Aslam; Samreen Riaz (Biological Trace Element Research, 2024)

Changes monitoring in Hongjiannao Lake from 1987 to 2023 using Google Earth Engine and analysis of climatic and anthropogenic forces - Md. Enamul Huq; Xijun Wu; Akib Javed; Ying Dong; Bingbing Li; David Lopez-Carr; Jiang Wu; Jing Liu; Yaning Zhang; Fanping Zhang; Muhammad Riaz; Md. Nazirul Islam Sarker; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Investigating the potential of 1,2,4-triazoles as corrosion inhibitors for copper and steel: A comprehensive review - Aqsa Ashraf; Naheed Riaz; Saima Muzaffar; Muhammad Atif; Bushra Bashir (Next Research, 2024)

Health risk assessment of lead and cadmium exposure from food and snuff in Pakistani population - Hamza Shafiq; Mamoona Amir; Salman Asghar; Aneela Hameed; Muhammad Riaz (Journal of Trace Elements in Medicine and Biology, 2024)

GmSTOP1-3 regulates flavonoid synthesis to reduce ROS accumulation and enhance aluminum tolerance in soybean - Guoxuan Liu; Dongqian Li; Huafu Mai; Xiaoying Lin; Xing Lu; Kang Chen; Ruotong Wang; Muhammad Riaz; Jiang Tian; Cuiyue Liang (Journal of Hazardous Materials, 2024)

Soil microbiological assessment on diversified annual cropping systems in China - Hao Xia; Jia Shen; Muhammad Riaz; Chaolong Zu; Fei Yu; Yifeng Yan; Bo Liu; Chaoqiang Jiang (Journal of Environmental Management, 2024)

Nutraceutical tablets: Manufacturing processes, quality assurance, and effects on human health - Muhammad Faisal Manzoor; Sakhawat Riaz; Deepak Kumar Verma; Muhammad Waseem; Gulden Goksen; Anwar Ali; Xin-An Zeng (Food Research International, 2024)

Utilizing Cinnamomum verum (a culinary spice), as a functional food ingredient ameliorating hypercholesterolemia: In-vivo, in-vitro, and in-silico multi-model analysis - Mahnoor Bano; Muhammad Khurram Waqas; Talha Ali Chohan; Fakhra Batool; Aamir Mushtaq; Yahya I. Asiri; Mohd. Zaheen Hassan; Md Ali Mujtaba; Md. Khalid Anwer; Muhammad Irfan Sidique; Ayesha Riaz; Umair Khurshid; et al. (Food Bioscience, 2024)

Food safety profile of university food handlers in Bangladesh: A multicenter cross-sectional study - Tahsin Ahmed Rupok; Shahnaz Parvin Sweety; Mst. Mahfuza Rahman; Most. Tasfia Rahman; Fahmida Zaman; Muhammad Radone Ahmed; Tanvirul Islam; Md. Nurnobi Islam; Md. Masud Rana; Abdur Rahman Riaz; Md. Golam Sadik (Food and Humanity, 2024)

Methodology comparison of environmental sediment fungal community analysis - Xinlei Li; Yongjie Li; Yingying Wang; Yanyan Liu; Luqman Riaz; Qingqing Wang; Xiangpeng Zeng; Zhao Qin; Muhammad Irfan; Qingxiang Yang (Environmental Research, 2024)

Taxifolin: A flavonoid in the freezing medium augments post-thaw semen quality and in vivo fertility potential of buffalo bull spermatozoa - Hussain Ahmed; Muhammad Umar Ijaz; Mehreen Riaz; Farhad Ullah; Haney Samir; Muhammad Shuaib; Ayman A. Swelum (Cryobiology, 2024)

Association of polymorphism of NLRP3, ICAM-1, PTPN22, INS genes in childhood onset type 1 diabetes in a Pakistani population - Anjum Jabeen; Samreen Riaz; Muhammad Usman; Asia Parveen; Maryam Mukhtar; Abdul Wajid; Atif Hanif; Andleeb Batool (Molecular Biology Reports, 2024)

Notes on species of Sporisorium and Ustilago from Pakistan - Sadiq Ullah; Najam-ul-Sehar Afshan; Aamna Ishaq; Maria Riaz; Muhammad Fiaz; Abdul Nasir Khalid; Mary Catherine Aime (Mycological Progress, 2024)

Modeling the dynamics of dengue fever with double susceptibility and optimal control strategies - Muhammad Younas Khan; Saif Ullah; Muhammad Farooq; Muhammad Bilal Riaz (Modeling Earth Systems and Environment, 2024)

Metagenomic approaches and opportunities in arid soil research - Muhammad Riaz Ejaz; Kareem Badr; Zahoor Ul Hassan; Roda Al-Thani; Samir Jaoua (Science of The Total Environment, 2024)

Role of pressmud compost for reducing toxic metals availability and improving plant growth in polluted soil: Challenges and recommendations - Altaf Hussain Lahori; Maira Tunio; Samreen Riaz Ahmed; Monika Mierzwa-Hersztek; Viola Vambol; Ambreen Afzal; Anila Kausar; Sergij Vambol; Aqsa Umar; Atif Muhammad (Science of The Total Environment, 2024)

Exploring fruit ripening methods: Conventional, artificial, and novel approaches for quality and health - Usama Nasir; Amir Ismail; Muhammad Riaz; Kashif Razzaq; Sajid Ali; Ajaz Hussain; Mavra Ameen; Asifa Saif; Farwa Aslam; Carlos Augusto Fernandes de Oliveira (Food Control, 2024)

Failure mechanism of a massive fault–controlled rainfall–triggered landslide in northern Pakistan - Muhammad Tayyib Riaz; Muhammad Basharat; Khawaja Shoaib Ahmed; Yasir Sirfraz; Amir Shahzad; Nisar Ali Shah (Landslides, 2024)

Protective Effect of Proline Against Boron Deficiency on Photosynthesis and Proline Metabolites in Cotton (Gossypium hirsutum L.) at Different Growth Stages - Jin Cheng; Zijun Zeng; Riaz Muhammad; Zeinab El-Desouki; Cuncang Jiang (Journal of Plant Growth Regulation, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Experimental investigation of the wake of tandem cylinders using pivoted flapping mechanism for piezoelectric flag - Muhammad Mahad Shah; Rizwan Mahmood; Usman Latif; Emad Uddin; Adnan Munir; Ming Zhao; Hafiz Hamza Riaz (Ocean Engineering, 2024)

Exposure Levels, Health Risks, Spatially Distribution, Multivariate Statistics and Positive Matrix Factorization Model of Heavy Metals from Wild solid Waste Dumpsites - Predrag Ilić; Svetlana Ilić; Abdur Rashid; Zain Mushtaq; Sanja Mrazovac Kurilić; Ljiljana Stojanović Bjelić; Dragana Nešković Markić; Zia Ur Rahman Farooqi; Muhammad Yousuf Jat Baloch; Tariq Mehmood; Zahid Ullah; Sobia Riaz (Water, Air, & Soil Pollution, 2024)

Boron toxicity in plants: understanding mechanisms and developing coping strategies; a review - Shaopeng Zhao; Md. Enamul Huq; Shah Fahad; Muhammad Kamran; Muhammad Riaz (Plant Cell Reports, 2024)

Exploring the underlying pharmacological, immunomodulatory, and anti-inflammatory mechanisms of phytochemicals against wounds: a molecular insight - Anfah Riaz; Shaukat Ali; Muhammad Summer; Shehzeen Noor; Laiba Nazakat; Aqsa; Muhammad Sharjeel (Inflammopharmacology, 2024)

Microbial regulatory mechanisms of disease-resistant tobacco varieties in the prevention and control of bacterial wilt disease - Hao Xia; Jia Shen; Muhammad Riaz; Huaying Yang; Qing Dong; Chaolong Zu; Fei Yu; Yifeng Yan; Jiaxin Li; Bo Liu; Chaoqiang Jiang (Applied Soil Ecology, 2024)

Pomegranate Peel Extract as 6-Phosphogluconate Dehydrogenase (6PGD) Inhibitor for Treatment of Breast Cancer - Saba Riaz; Azhar Rasul; Matloob Ahmad; Muhammad Asrar; Mudassir Hassan (Cell Biochemistry and Biophysics, 2024)

Recent advances of MXene@MOF composites for catalytic water splitting and wastewater treatment approaches - Samreen Afzal; Aziz ur Rehman; Tayyaba Najam; Ismail Hossain; Mostafa A.I. Abdelmotaleb; Sundas Riaz; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Chemosphere, 2024)

Inflammatory response of nanoparticles: Mechanisms, consequences, and strategies for mitigation - Muhammad Summer; Rimsha Ashraf; Shaukat Ali; Horacio Bach; Shehzeen Noor; Qudsia Noor; Saima Riaz; Rana Rashad Mahmood Khan (Chemosphere, 2024)

Effect of supplementing epinephrine in maturation media on in-vitro developmental competence of cattle and buffalo oocytes - Abdul Khaliq; Muhammad Ameer Hamza; Talha Ashraf; Ali Husnain; Muhammad Yaseen; Abdul Rehman; Muhammad Binyameen; Muhammad Yasir Zahoor; Amjad Riaz (Theriogenology, 2024)

Sustainability and photocatalytic performance of MOFs: Synthesis strategies and structural insights - Zeshan Ali Sandhu; Umme Farwa; Muhammad Danish; Muhammad Asam Raza; Aqib Talib; Hifza Amjad; Rukhmah Riaz; Abdullah G. Al-Sehemi (Journal of Cleaner Production, 2024)

Co-application of biochar and potassium fertilizer improves soil potassium availability and microbial utilization of organic carbon: A four-year study - Hao Xia; Jiyuan Wang; Muhammad Riaz; Saba Babar; Yuxuan Li; Xiangling Wang; Xiaoyang Xia; Bo Liu; Cuncang Jiang (Journal of Cleaner Production, 2024)

Impact of sea surface temperature in the Arabian Sea on the variability of Summer Monsoon Rainfall over Pakistan Region - Muhammad Adeel; Atteeq Razzak; Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal (Dynamics of Atmospheres and Oceans, 2024)

Effect of naringenin on post-thaw quality, fertility-associated gene expression and fertilization potential of buffalo (Bubalus bubalis) bull sperm - Ghulam Shabbir Khan; Muhammad Zahid Tahir; Muhammad Yasir Zahoor; Hifz-ul-Rahman; Amjad Riaz (Cryobiology, 2024)

Uptake, Agglomeration, and Detoxification of Trace Metals and Metalloids in Plants - Babar Hussain; Aqleem Abbas; Aansa Rukya Saleem; Luqman Riaz; Shafeeq Ur Rahman; Shibin Liu; Shengyan Pu; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2024)

Foliar Application of Moringa and Mint Leaf Extracts Enhances Carnation Growth and Flower Yield Under Saline Conditions by Improving Plant Defense Mechanism - Hafiza Muniba Din Muhammad; Muhammad Akbar Anjum; Riaz Ahmad; Sezai Ercisli (Journal of Plant Growth Regulation, 2024)

Alleviating Drought Stress in Strawberry Plants: Unraveling the Role of Paclobutrazol as a Growth Regulator and Reducer of Oxidative Stress Induced by Reactive Oxygen and Carbonyl Species - Khansa Saleem; Muhammad Ahsan Asghar; Ali Raza; Kaiwen Pan; Abd Ullah; Hafiz Hassan Javed; Mahmoud F. Seleiman; Shakeel Imran; Sajid Mehmood Nadeem; Khurram Shehzad Khan; Junbo Du; Fei Xu; et al. (Journal of Plant Growth Regulation, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Long-term raw crop residue but not burned residue incorporation improved soil multifunctionality in semi-arid agroecosystems - Aqeel Ahmad; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Awais Shakoor; Shahid Iqbal; Asam Riaz; Anjum Zahid; Stephen James Chapman (Soil and Tillage Research, 2024)

Role of social networks and entrepreneurial success: Understanding the dynamics of knowledge acquisition and green entrepreneurial orientation - Saba Riaz; Wang Yanqing; Muhammad Ishtiaq Ishaq; Ali Raza; Roheel Ahmad Siddiqui (Journal of Cleaner Production, 2024)

CRISPR-Cas9 mediated understanding of plants’ abiotic stress-responsive genes to combat changing climatic patterns - Muhammad Waqas Choudry; Rabia Riaz; Pashma Nawaz; Maria Ashraf; Bushra Ijaz; Allah Bakhsh (Functional & Integrative Genomics, 2024)

Phytochemical-mediated regulation of aflatoxigenic fungi contamination in a shifting climate and environment - Shah Zaman; Nasrullah Khan; Muhammad Zahoor; Riaz Ullah; Ahmed Bari; Sohail (Environmental Geochemistry and Health, 2024)

Molecular identification and characterization of iris yellow spot virus (IYSV) and garlic virus X (GVX) infecting Allium species - Muhammad Usman Shahid; Abid Riaz; Tahira Shafique; Mayasar I. Al-zaban; Diaa Abd El-Moneim; Sheikh Mansoor; Yong Suk Hung; Hyeon-Jin Sun (Plant Biotechnology Reports, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Enhancing drought tolerance in broccoli (Brassica oleracea L.) through melatonin application: Physiological and biochemical insights into growth, photosynthesis, and antioxidant defense mechanisms - Hasan Sardar; Muhammad Shafiq; Safina Naz; Sajid Ali; Riaz Ahmad; Shaghef Ejaz (Biocatalysis and Agricultural Biotechnology, 2024)

Comparative role of charcoal, biochar, hydrochar and modified biochar on bioavailability of heavy metal(loid)s and machine learning regression analysis in alkaline polluted soil - Altaf Hussain Lahori; Samreen Riaz Ahmed; Monika Mierzwa-Hersztek; Madiha Afzal; Ambreen Afzal; Shella Bano; Maria Taj Muhammad; Aqsa Aqsa; Viola Vambol; Sergij Vambol (Science of The Total Environment, 2024)

Exposure to heavy metals, antioxidant status, and the interaction of single nucleotide polymorphisms in the genes CAT rs7943316, GSTP1 rs1695, as well as GSTM1 and GSTT1 genes, among workers in occupational settings - Sosan Andleeb Khan; Syed Muhammad Nurulain; Rashid Nazir Qureshi; Amina Zafar; Zarish Riaz; Aneela Shoukat; Zahid Muneer; Nazia Bibi; Saqlain Raza; Sabir Hussain; Syed Tahir Abbas Shah (Environmental Toxicology and Pharmacology, 2024)

Unveiling the chemical profile, synergistic antibacterial and hemolytic effects of Cymbopogon citratus and Tachyspermum ammi leaves - Shabbir Hussain; Amina Zahid; Muhammad Imran; Shazma Massey; Muhammad Riaz; Muhammad Sagir; Muhammad Shahid; Wissem Mnif; Shahid Iqbal; Munawar Iqbal; Arif Nazir (Biocatalysis and Agricultural Biotechnology, 2024)

Mass-spectrometric analysis of APOB polymorphism rs1042031 (G/T) and its influence on serum proteome of coronary artery disease patients: genetic-derived proteomics consequences - Muneeza Zafar; Imran Riaz Malik; Munazza Raza Mirza; Fazli Rabbi Awan; Arkadiusz Nawrocki; Misbah Hussain; Haq Nawaz Khan; Shahid Abbas; Muhammad Iqbal Choudhary; Martin R. Larsen (Molecular and Cellular Biochemistry, 2024)

Acid-modified cotton straw biochar has instructive for the improvement of saline-alkali soil - Xiaoyang Xia; Muhammad Riaz; Saba Babar; Yuxuan Li; Xiangling Wang; Jiyuan Wang; Cuncang Jiang (Journal of Soils and Sediments, 2024)

Heavy Metal Stress in Medicinal Plants: Detoxification Mechanisms, Antioxidants, and Implications for Human Health - Muhammad Waheed Riaz; Tong Wu; Quaid Hussain; Fasih Ullah Haider; Weiwei Jiang; Qingsong Shao; Muhammad Aamir Manzoor; Bingcong Xing (Journal of Soil Science and Plant Nutrition, 2024)

Physico-mechanical characterization of eco-friendly gypsum composites incorporating shredded surgical face masks - Muhammad Hassan Javed; Muhammad Rizwan Riaz; Rizwan Azam; Muhammad Kashif; Anam Fatima (Innovative Infrastructure Solutions, 2024)

Pyridine-2,6-Dicarboxylic Acid As a Facile and Highly Selective “Turn-Off” Fluorimetric Chemosensor for Detection of Cu (II) Ions in Aqueous Media - Javed Hussain Shah; Shahzad Sharif; Muhammad Shahbaz; Bilal Riaz; Sundas Shahzad; Onur Şahin; Khurram Shahzad Munawar; Hijaz Ahmad; Essam A. Al-Ammar (Journal of Fluorescence, 2024)

Impact of dichromatic lighted incubation on hatching result and post-hatch performance of broiler chickens - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Saima (Tropical Animal Health and Production, 2024)

Assessment of heavy metals level in chicken with indeterminate analysis in localities of Lahore, Pakistan - Naveed Ahmad; Usama Afzal; Ramna Zafar; Muhammad Arslan; Saira Riaz; Shahzad Naseem; Muhammad Naeem; Adeena Fatima; Mubashar Ali; Muhammad Aslam (Environmental Monitoring and Assessment, 2024)

Occurrence of natural enemies in maize and the predatory potential of selected arthropods against fall armyworm in Multan, Pakistan - Saleem Riaz; Muhammad Ishtiaq; Fawad Zafar Ahmad Khan; Ghulam Ali; Mirza Abid Mehmood; Muhammad Sohail Qamar Zaman (International Journal of Tropical Insect Science, 2024)

Influences of tobacco straw return with lime on microbial community structure of tobacco-planting soil and tobacco leaf quality - Chaoqiang Jiang; Chaolong Zu; Muhammad Riaz; Chen Li; Qifa Zhu; Hao Xia; Qing Dong; Jia Shen (Environmental Science and Pollution Research, 2024)

From stress to success: Silicon and nano-silicon strategies for enhancing fruit yield and quality in cadmium-exposed trees - Riaz Ahmad; Hafiza Muniba Din Muhammad; Safina Naz; Rahul Kumar Tiwari; Milan Kumar Lal; Parvaiz Ahmad; Muhammad Ahsan Altaf (South African Journal of Botany, 2024)

Alleviation of cotton growth suppression caused by salinity through biochar is strongly linked to the microbial metabolic potential in saline-alkali soil - Xiangling Wang; Muhammad Riaz; Xiaoyang Xia; Saba Babar; Zeinab El-Desouki; Yuxuan Li; Jiyuan Wang; Cuncang Jiang (Science of The Total Environment, 2024)

Development of red mud-modified geopolymer coating with radiative cooling effect for footway application - Ning Yang; Sizhe Xue; Muhammad Riaz Ahmad; Qingdong Xuan; Ming-Feng Kai; Jian-Guo Dai (Journal of Cleaner Production, 2024)

Ecological characteristics of sugar beet plant and rhizosphere soil in response to high boron stress: A study of the remediation potential - Jialu Huo; Baiquan Song; Xiaochen Lin; Muhammad Riaz; Xiaoyu Zhao; Shangxuan Liu; Qingqing She (Journal of Environmental Management, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Strategies for Crossing Biological Barriers in Drug Delivery - Muhammad Awais; Salma Batool; Mahnoor Khan; Laiba Asim; Rabia Riaz; Rimsha Zafar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Toxicological assessment of dietary exposure of polyethylene microplastics on growth, nutrient digestibility, carcass and gut histology of Nile Tilapia (Oreochromis niloticus) fingerlings - Muhammad Mahmood; Syed Makhdoom Hussain; Pallab K. Sarker; Shafaqat Ali; Muhammad Saleem Arif; Nadia Nazish; Danish Riaz; Nisar Ahmad; Bilal Ahamad Paray; Adan Naeem (Ecotoxicology, 2024)

Multi-Elemental Chemostratigraphy, Sequence Development, Depositional History, and Environmental Importance of Early Eocene Red Beds (Kuldana Formation) in NW Himalayas, Pakistan - Amir Shahzad; George Kontakiotis; Thierry Adatte; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Hammad Tariq Janjuhah; Evangelia Besiou (Journal of Earth Science, 2024)

2D MXenes and their composites; design, synthesis, and environmental sensing applications - Naseer Ahmad; Sufian Rasheed; Abrar Mohyuddin; Batool Fatima; Muhammad Ikram Nabeel; Muhammad Tariq Riaz; Muhammad Najam-ul-Haq; Dilshad Hussain (Chemosphere, 2024)

RNA based gene silencing modalities to control insect and fungal plant pests – Challenges and future prospects - Muhammad Waqas Choudry; Pashma Nawaz; Neelam Jahan; Rabia Riaz; Bilal Ahmed; Muhammad Hassan Raza; Zohaib Fayyaz; Kausar Malik; Samia Afzal (Physiological and Molecular Plant Pathology, 2024)

Eocene nannofossils and paleoenvironmental reconstruction of the Kuldana Formation in Yadgar area, Muzaffarabad, northern Pakistan - Amir Shahzad; Jahanzeb Khan; Muhammad Hanif; Claudia Baumgartner-Mora; Yasir Sarfraz; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Peter O. Baumgartner; Munir ul Hassan Munir; Adnan Wazir (Palaeoworld, 2024)

Variations in rhizosphere soil dominant and pathogenic flora improve boron-efficient Beta vulgaris L. yield under boron deficit - Shangxuan Liu; Baiquan Song; Shafaque Sehar; Muhammad Faheem Adil; Xiaochen Lin; Jialu Huo; Xiaoyu Zhao; Muhammad Riaz (Journal of Cleaner Production, 2024)

Modeling the linkage between climate-tech, energy transition, and CO2 emissions: Do environmental regulations matter? - Mahmood Ahmad; Zahoor Ahmed; Muhammad Riaz; Xiyue Yang (Gondwana Research, 2024)

Phytochemical, nutraceutical and oxidative stress modulation activities of Solanum villosum Mill. leaf and berry extracts - Iqra Riaz; Yamin Bibi; Muhammad Arshad; Muhammad Sheeraz Ahmad; Nabeela Ahmad; Abdul Qayyum (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Understanding the origin of ancient carbonate ooids: recent findings - Muhammad Riaz; Santanu Banerjee; Khalid Latif; Ziliang Liu; Mohamed S. Ahmed; Douaa Fathy (International Geology Review, 2024)

First insights into per-and polyfluoroalkyl substance contamination in edible fish species of the Indus water system of Pakistan - Rahat Riaz; Muhammad Yasir Abdur Rehman; Muhammad Junaid; Taimoor Iqbal; Jawad Aslam Khan; Yanran Dong; Linxia Yue; Yupeng Chen; Nan Xu; Riffat Naseem Malik (Chemosphere, 2024)

Utilizing thiourea-modified biochars to mitigate toxic metal pollution and promote mustard (Brassica campestris) plant growth in contaminated soils - Irfan Saleem; Samreen Riaz Ahmed; Altaf Hussain Lahori; Monika Mierzwa-Hersztek; Shella Bano; Ambreen Afzal; Maria Taj Muhammad; Madiha Afzal; Viola Vambol; Sergij Vambol; Zengqiang Zhang (Journal of Geochemical Exploration, 2024)

Research on phytotoxicity assessment and photosynthetic characteristics of nicosulfuron residues on Beta vulgaris L - Xiaoyu Zhao; Qing Xie; Baiquan Song; Muhammad Riaz; Milan Kumar Lal; Longfeng Wang; Xiaochen Lin; Jialu Huo (Journal of Environmental Management, 2024)

Alterations in the composition and metabolite profiles of the saline-alkali soil microbial community through biochar application - Xiangling Wang; Muhammad Riaz; Saba Babar; Zeinab Eldesouki; Bo Liu; Hao Xia; Yuxuan Li; Jiyuan Wang; Xiaoyang Xia; Cuncang Jiang (Journal of Environmental Management, 2024)

Integration of chitosan coating and short-term hypobaric treatment extends postharvest life and upregulates defense-related enzymes in apple fruit - Syed Umair Shah; Majid S. Hashmi; Muhammad Rafiullah Khan; Ayaz Ahmad; Aysha Riaz; Yosef Al Shoffe; Said Wahab; Muhammad Ayub; Antonio Ippolito (European Journal of Plant Pathology, 2024)

From biodiversity hotspot to conservation hotspot: assessing distribution, population structure, associated flora and habitat geography of threatened Himalayan Yew in temperate forest ecosystems of Kashmir - Hamayun Shaheen; Arbaz Attique; Malik Talha Riaz; Muhammad Manzoor; Raja Waqar Ahmed Khan; Muhammad Tayyib Riaz (Biodiversity and Conservation, 2024)

Impact of Various Combinations of Organic and Inorganic Fertilizers on Fruit Production and Quality of ‘Kinnow’ Mandarin (Citrus reticulata Blanco.) - Muhammad Asim; Faisal Hayat; Tehseen Ashraf; Fakhara Khanum; Juan Li; Yang Peng; Yanxiao Ma; Shahid Iqbal; Ummara Khan; Sitwat Riaz; Panfeng Tu; Fiaz Hussain; et al. (Applied Fruit Science, 2024)

Fucoidan-based nanomaterial and its multifunctional role for pharmaceutical and biomedical applications - Muhammad Waheed Iqbal; Tahreem Riaz; Shahid Mahmood; Muhammad Bilal; Muhammad Faisal Manzoor; Sarmad Ahmad Qamar; Xianghui Qi (Critical Reviews in Food Science and Nutrition, 2024)

Remote sensing and GIS based multi-criteria analysis approach with application of AHP and FAHP for structures suitability of rainwater harvesting structures in Lai Nullah, Rawalpindi, Pakistan - Rashid Ahmad; Hamza Farooq Gabriel; Farooq Alam; Riaz Zarin; Abdur Raziq; Muhammad Nouman; Hsu-Wen Vincent Young; Yuei-An Liou (Urban Climate, 2024)

Fundamental opportunities and challenges of nutraceutical noodles enriched with agri-food by-products - Zahoor Ahmed; Jin Chen; Tabussam Tufail; Anam Latif; Muhammad Arif; Riaz Ullah; Ali S. Alqahtani; Bin Xu (Trends in Food Science & Technology, 2024)

A practical tool for structural design optimization of steel frames: development and application for parametric analysis - Umair Ali; Rizwan Azam; Mansoor Shakeel; Muhammad Adil; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2024)

Radon concentration in spring water as an indicator of seismic activity: a case study of the Muzaffarabad Fault in Pakistan - Sayed Qamar Abbas; Jahanzeb Khan; Muhammad Tayyib Riaz; Muhammad Rafique; Ali Zaman; Sajjad Khan (Environmental Monitoring and Assessment, 2024)

Characterization of water-deficit tolerance in Upland cotton (Gossypium hirsutum L.) assessing morphological, biochemical, molecular and yield attributes - Muhammad Saeed; Muhammad Naeem; Alia Javed; Shagufta Perveen; Iqra Sajjad; Muhammad Zaid Yousaf; M. Shahid Munir Chohan; Muhammad Riaz; Sana Ullah; Xianliang Song (Acta Physiologiae Plantarum, 2024)

Modulation of metal transporters, oxidative stress and cell abnormalities by synergistic application of silicon and titanium oxide nanoparticles: A strategy for cadmium tolerance in rice - Mingyu Lai; Fozia Ghouri; Samreen Sarwar; Sarah Owdah Alomrani; Muhammad Riaz; Fasih Ullah Haider; Jingwen Liu; Muhammad Imran; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Chemosphere, 2023)

Unraveling the combined deleterious effects of ochratoxin A and atrazine upon broiler’s health: Toxicopathological, serum biochemical and immunological perspectives - Aisha Khatoon; Muhammad Yasir Nawaz; Ghazala Mehboob; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Rao Zahid Abbas; Muhammad Umar Ijaz; Bilal Murtaza; Sheraz Ahmed Bhatti; Zain ul Abidin; Aamir Riaz Khan (Toxicon, 2023)

Unraveling the mechanisms of cadmium toxicity in horticultural plants: Implications for plant health - Muhammad Ahsan Altaf; Safina Naz; Ravinder Kumar; Hasan Sardar; Muhammad Azher Nawaz; Awadhesh Kumar; Priyanka Lal; Riaz Ahmad; Faisal Hayat; Muneeb Ahmad Wani; Rahul Kumar Tiwari; Milan Kumar Lal (South African Journal of Botany, 2023)

Current understanding of boosting power of salicylic acid for abiotic stress tolerance in horticultural crops - Muhammad Ahsan Altaf; Rabia Shahid; Priyanka Lal; Riaz Ahmad; Faisal Zulfiqar; Awadhesh Kumar; Faisal Hayat; Ravinder Kumar; Milan Kumar Lal; Safina Naz; Rahul Kumar Tiwari (South African Journal of Botany, 2023)

Effect of co-application of straw and various nitrogen fertilizers on N2O emission in acid soil - Yuxuan Li; Riaz Muhammad; Babar Saba; Hao Xia; Xiangling Wang; JiYuan Wang; Xiaoyang Xia; Jiang Cuncang (Journal of Environmental Management, 2023)

Abiogenic silicon: Interaction with potentially toxic elements and its ecological significance in soil and plant systems - Babar Hussain; Luqman Riaz; Kun Li; Kashif Hayat; Naveed Akbar; Muhammad Zakwan Hadeed; Bowei Zhu; Shengyan Pu (Environmental Pollution, 2023)

Chemical and mechanical coating of sulfur on baby corn biochar and their role in soil Pb availability, uptake, and growth of tomato under Pb contamination - Jing Ma; Ziyi Hua; Sana Noreen; Zaffar Malik; Muhammad Riaz; Muhamamd Kamran; Shafaqat Ali; Mohamed S. Elshikh; Fu Chen (Environmental Pollution, 2023)

Impact of different light intensities to Japanese quail eggs on hatching results and post-hatch performance - Shaheryar Ali; Shahid Sherzada; Muhammad Usman; Ehsaan Ullah Khan; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Seaweed Application Enhanced the Growth and Yield of Pea (Pisum sativum L.) by Altering Physiological Indices - Safina Naz; Hafiza Muniba Din Muhammad; Muhammad Ramzan; Bushra Sadiq; Riaz Ahmad; Saqib Ali; Abdulaziz Abdullah Alsahli; Muhammad Ahsan Altaf (Journal of Soil Science and Plant Nutrition, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Relaxin (a regulatory-peptide) enhances cryotolerance, fertility potential and plasma reproductive hormones of Nili Ravi buffalo (Bubalus bubalis) during low breeding season - Hussain Ahmed; Sarwat Jahan; Muhammad Umar Ijaz; Mehreen Riaz; Farhad Ullah (Research in Veterinary Science, 2023)

“ Assessing the impact of biochar on microbes in acidic soils: Alleviating the toxicity of aluminum and acidity” - Hao Xia; Muhammad Riaz; Saba Babar; Lei Yan; Yuxuan Li; Xiangling Wang; Jiyuan Wang; Cuncang Jiang (Journal of Environmental Management, 2023)

Effects of micro(nano)plastics on soil nutrient cycling: State of the knowledge - Muhammad Salam; Huaili Zheng; Yingying Liu; Aneeqa Zaib; Syed Aziz Ur Rehman; Nimra Riaz; Moataz Eliw; Faisal Hayat; Hong Li; Fayuan Wang (Journal of Environmental Management, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Regulation of proline metabolism, AsA-GSH cycle, cadmium uptake and subcellular distribution in Brassica napus L. under the effect of nano-silicon - Shaopeng Zhao; Muhammad Kamran; Muhamamd Rizwan; Shafaqat Ali; Lei Yan; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Riaz (Environmental Pollution, 2023)

Nano priming for boosting growth and resilience in crops under abiotic stresses - Faizan Khalid; Kanza Asif; Yumna Rasheed; Humaira Ashraf; Muhammad Faisal Maqsood; Shamsa Rana; Usman Zulfiqar; Nargis Naz; Muhammad Shahbaz; Rehana Sardar; Zunaira Riaz (Biocatalysis and Agricultural Biotechnology, 2023)

Eliciting the Response of Rhizospheric Soil Microbial Community Structure to Zinc Amendment: A Case Study of Sugar Beet Cultivation in Black Soil - Qiue Jia; Baiquan Song; Jialu Huo; Xin Song; Yan Wang; Muhammad Faheem Adil; Muhammad Riaz; Milan Kumar Lal; Hayssam M. Ali (Sugar Tech, 2023)

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Biohermal complex dominated by microbial carbonates from the early Miaolingian (lower Cambrian) Maozhuang Formation, North China - Mingxiang Mei; Muhammad Riaz; Khalid Latif; Ziliang Liu; Mohamed S. Ahmed; Douaa Fathy (Facies, 2023)

Potential application of melatonin in reducing boron toxicity in rice seedlings through improved growth, cell wall composition, proline, and defense mechanisms - Xinyu Li; Muhammad Kamran; Muhammad Hamzah Saleem; Abdullah Ahmed Al-Ghamdi; Fahad M. Al-Hemaid; Mohamed S. Elshikh; Shaopeng Zhao; Muhammad Riaz (Chemosphere, 2023)

Alleviation of arsenic toxicity-induced oxidative stress in lemon grass by methyl jasmonate - Khansa Saleem; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Ali Raza; Mahmoud F. Seleiman; Abd Ullah; Altafur Rahman; Sufyan Iqbal; Aamir Hanif; Shakeel Imran; Sajid Mahmood Nadeem; Junbo Du; et al. (South African Journal of Botany, 2023)

Moringa oleifera: Processing, phytochemical composition, and industrial applications - Karima Gharsallah; Leila Rezig; Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; M.Abbas Ali; Sook Chin Chew (South African Journal of Botany, 2023)

A game theory approach to land acquisition conflicts in Pakistan - Ahsan Shafi; Zhanqi Wang; Muhsan Ehsan; Faizan Ahmed Riaz; Muhammad Rashid Ali; Feng Xu (Land Use Policy, 2023)

The protective role of tetraploidy and nanoparticles in arsenic-stressed rice: Evidence from RNA sequencing, ultrastructural and physiological studies - Fozia Ghouri; Munazzam Jawad Shahid; Jingwen Liu; Lixia Sun; Muhammad Riaz; Muhammad Imran; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Journal of Hazardous Materials, 2023)

Photocatalytic and Antibacterial Potential of Chitosan Supported Nickel Oxide/Zinc Oxide Composite Synthesized by Alcohothermal Method - Amna Yasin; Tousif Hussain; Riaz Ahmad; Urooj Shuaib; Muhammad Amjad; Sajjad Ahmad; M. Imranullah (Water, Air, & Soil Pollution, 2023)

The Dynamics of the Relationship Between Water Availability, Water Equity, Economic Benefits and Water User Associations’ Performance: A PLS-SEM Approach - Mohsin Riaz; Muhammad Ashfaq; Ismet Boz; Pomi Shahbaz (Water Resources Management, 2023)

Semi-quantitative landslide risk assessment of district Muzaffarabad, northwestern Himalayas, Pakistan - Muhammad Tayyib Riaz; Muhammad Basharat; Maria Teresa Brunetti; Malik Talha Riaz (Stochastic Environmental Research and Risk Assessment, 2023)

Smart reprogramming of jujube germplasm against salinity tolerance through molecular tools - Meryam Manzoor; Safina Naz; Hafiza Muniba Din Muhammad; Riaz Ahmad (Functional & Integrative Genomics, 2023)

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Peanut shell biochar in acidic soil increases nitrogen absorption and photosynthesis characteristics of maize under different nitrogen levels - Hao Xia; Muhammad Riaz; Bo Liu; YuXuan Li; Zeinab El-Desouki; Cuncang Jiang (Environment, Development and Sustainability, 2023)

Microbiological mechanism for “production while remediating” in Cd-contaminated paddy fields: A field experiment - Jiguang Gu; Fang Guo; Lihong Lin; Jiexiang Zhang; Weimin Sun; Riaz Muhammad; Haojie Liang; Dengle Duan; Xingying Deng; Zheng Lin; Yifan Wang; Yuming Zhong; et al. (Science of The Total Environment, 2023)

Can the co-application of biochar and different inorganic nitrogen fertilizers repress N2O emissions in acidic soil? - Yuxuan Li; Riaz Muhammad; Babar Saba; Hao Xia; Xiangling Wang; JiYuan Wang; Cuncang Jiang (Environmental Research, 2023)

Emmer wheat (Triticum dicoccum)–based intervention in Japanese quail’s diet and its impact on performance, carcass yield, meat fatty acids, and fecal volatile fatty acids - Mükremin Ölmez; Kanber Kara; Muhammad Shazaib Ramay; Roshan Riaz; Tarkan Şahin (Tropical Animal Health and Production, 2023)

Exogenous Application of Melatonin Improves the Growth and Productivity of Two Broccoli (Brassica oleracea L.) Cultivars Under Salt Stress - Hasan Sardar; Muhammad Arif Ramzan; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Muhammad Ahsan Altaf (Journal of Plant Growth Regulation, 2023)

Improved photocatalytic decolorization of reactive black 5 dye through synthesis of graphene quantum dots–nitrogen-doped TiO2 - Muhammad Saqib Khan; Nadia Riaz; Saeed Rehman; Liu Chenhui; Ahson Jabbar Shaikh; Muhammad Arfan; Iftikhar Zeb; Muhammad Arshad; Farhan Hafeez; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Spectroscopic fingerprinting, pollution characterization, and health risk assessment of potentially toxic metals from urban particulate matter - Abdul Rehman; Guijian Liu; Balal Yousaf; Samra Ijaz; Samina Irshad; Ayesha Imtiyaz Cheema; Muhammad Umair Riaz; Aniqa Ashraf (Environmental Science and Pollution Research, 2023)

Anar Phali (Opuntia ficus) juice extract as a novel pollution-free source of natural betalain dye for wool yarn - Yousra Riaz; Samra Barkaat; Shahid Adeel; Fazal-ur-Rehman; Muhammad Ibrahim; Muhammad Zuber; Meral Ozomay; Shahnaz Parveen Khattak (Environmental Science and Pollution Research, 2023)

Increased health risk assessment in different vegetables grown under untreated sewerage irrigation regime due to higher heavy metals accumulation - Zeshan Hassan; Ammara Hassan; Muhaiman Riaz; Azhar Abbas Khan; Sami Ul-Allah; Umbreen Shehzad; Muhammad Khurshid; Ali Bakhsh; Jawad Munawar Shah; Zahid Manzoor (Environmental Science and Pollution Research, 2023)

Iron-modified biochar reduces nitrogen loss and improves nitrogen retention in Luvisols by adsorption and microbial regulation - Jiyuan Wang; Muhammad Riaz; Saba Babar; Hao Xia; Yuxuan Li; Xiaoyang Xia; Xiangling Wang; Cuncang Jiang (Science of The Total Environment, 2023)

Insight into mechanisms of biochar-fertilizer induced of microbial community and microbiology of nitrogen cycle in acidic soil - Hao Xia; Muhammad Riaz; Xiufeng Tang; Lei Yan; Zeinab El-Desouki; Yuxuan Li; Xiangling Wang; Jiang Cuncang (Journal of Environmental Management, 2023)

Epidemiological survey of bovine gammaherpesvirus 4 (BoHV-4) infection in cattle and buffalo from Pakistan - Anees Khalid; Aayesha Riaz; Arfan Yousaf; Irtaza Hassan Khan; Saif Ur-Rehman; Muhammad Moaeen-ud-Din; Song Li; Congli Tang; Muhammad Ali Shah; Murtaz-ul-Hasan (Veterinary Research Communications, 2023)

Influence of Biochar on Soil Properties and Morphophysiology of Sugar Beet Under Fomesafen Residues - Xingfan Li; Baiquan Song; Dawei Yin; Milan Kumar Lal; Muhammad Riaz; Xin Song; Wengong Huang (Journal of Soil Science and Plant Nutrition, 2023)

Bidirectional Regulation of Calcium L-Aspartate Nanoparticles for Trifoliate Orange (Poncirus trifoliate L.) Growth by Altering the Pectin Nanostructure - Yalin Liu; Lei Yan; Riaz Muhammad; Zijun Zeng; Jin Cheng; Cuncang Jiang (Journal of Plant Growth Regulation, 2023)

In-field deployable and facile nanosensor for the detection of pesticides residues - Naveed Akhtar Shad; Anam Munawar; Yasir Javed; Allah Rakha; Ahsan Riaz; Salah Ud Din; Iqra Zareef; Muhammad Munir Sajid; Muahmmad Farhan Khan; Sareen Akhtar; Midhat Salman (Analytica Chimica Acta, 2023)

Sulforaphane inclusion in a freezing medium augments post-thaw motility, functional and biochemical features, and fertility potential of buffalo (Bubalus bubalis) spermatozoa - Hussain Ahmed; Muhammad Umar Ijaz; Mehreen Riaz; Sarwat Jahan (Research in Veterinary Science, 2023)

Nano-silicon mediated alleviation of Cd toxicity by cell wall adsorption and antioxidant defense system in rice seedlings - Muhammad Riaz; Muhammad Kamran; Shah Fahad; Xiurong Wang (Plant and Soil, 2023)

Cottonseed oil: A review of extraction techniques, physicochemical, functional, and nutritional properties - Tahreem Riaz; Muhammad Waheed Iqbal; Shahid Mahmood; Iqra Yasmin; Ali Ahmad Leghari; Abdur Rehman; Anam Mushtaq; Khubaib Ali; Muhammad Azam; Muhammad Bilal (Critical Reviews in Food Science and Nutrition, 2023)

Recycling of red mud and flue gas residues in geopolymer aggregates (GPA) for sustainable concrete - Lan-Ping Qian; Muhammad Riaz Ahmad; Jian-Cong Lao; Jian-Guo Dai (Resources, Conservation and Recycling, 2023)

Effects of prepartum melatonin treatment and suckling on postpartum reproductive performance of Beetal goats under subtropical conditions - Muhammad Afzaal; Muhammad Irfan-ur-Rehman Khan; Waqas Ahmad; Amir Hayat; Qasir Abbas; Muhammad Arshad; Nasir Hameed; Imran Mohsin; Amjad Riaz (Small Ruminant Research, 2023)

Development of low-carbon alkali-activated materials solely activated by flue gas residues (FGR) waste from incineration plants - Muhammad Riaz Ahmad; Chandra Sekhar Das; Mehran Khan; Jian-Guo Dai (Journal of Cleaner Production, 2023)

Performance evaluation of phosphonium based deep eutectic solvents coated cerium oxide nanoparticles for CO2 capture - Tausif Ahmad; Jibran Iqbal; Mohamad Azmi Bustam; Muhammad Babar; Muhammad Bilal Tahir; Muhammad Sagir; Muhammad Irfan; Hafiz Muhammad Anwaar Asghar; Afaq Hassan; Asim Riaz; Lai Fatt Chuah; Awais Bokhari; et al. (Environmental Research, 2023)

Recent Innovations in Non-dairy Prebiotics and Probiotics: Physiological Potential, Applications, and Characterization - Fasiha Fayyaz Khan; Asma Sohail; Shakira Ghazanfar; Asif Ahmad; Aayesha Riaz; Kashif Sarfraz Abbasi; Muhammad Sohail Ibrahim; Mohammad Uzair; Muhammad Arshad (Probiotics and Antimicrobial Proteins, 2023)

Transmission efficiency of Cotton leaf curl Khokhran virus /Cotton leaf curl Multan betasatellite complex by two whitefly cryptic species in Pakistan - Muhammad Afzal; Shafqat Saeed; Hasan Riaz; Muhammad Ishtiaq; M. Habib ur Rahman (International Journal of Tropical Insect Science, 2023)

Isolation, characterization and larvicidal potential of indigenous soil inhabiting bacteria against larvae of southern house mosquito (Culex quinquefasciatus Say) - Sohaib Iftikhar; Muhammad Asam Riaz; Muhammad Zeeshan Majeed; Muhammad Afzal; Anam Ali; Mubshara Saadia; Zulfiqar Ali; Sohail Ahmed (International Journal of Tropical Insect Science, 2023)

Public awareness and willingness to pay for eliminating atmosphere pollution in Pakistan: A case study - Fanglin Li; Riaz Ahmad; Muhammad Abbas; Muhammad Irfan (Environment, Development and Sustainability, 2023)

Decision tree regression algorithm-based model for prediction of traffic-induced vibrations: development and application for parametric investigation - Muhammad Faraz Javaid; Rizwan Azam; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2023)

Separation and purification of syngas-derived hydrogen: A comparative evaluation of membrane- and cryogenic-assisted approaches - Ahmad Naquash; Muhammad Abdul Qyyum; Yus Donald Chaniago; Amjad Riaz; Fatma Yehia; Hankwon Lim; Moonyong Lee (Chemosphere, 2023)

Two polyamines -responsive WRKY transcription factors from Anoectochilus roxburghii play opposite functions on flower development - Bingcong Xing; Siqi Wan; Liyang Su; Muhammad Waheed Riaz; Lihong Li; Yulin Ju; Wangshu Zhang; Ying Zheng; Qingsong Shao (Plant Science, 2023)

Impact of rock-water interaction on hydrogeochemical characteristics of groundwater: Using multivariate statistical, water quality index and irrigation indices of chachro sub-district, thar desert, sindh, Pakistan - Muhammad Soomar Samtio; Asghar Ali alias Daahar Hakro; Taj Muhammad Jahangir; Abdul Shakoor Mastoi; Muhammad Farooque Lanjwani; Riaz Hussain Rajper; Rafique Ahmed Lashari; Muhammad Hassan Agheem; Muhammad Waseem Noonari (Groundwater for Sustainable Development, 2023)

Assessing the difference of biochar and aged biochar to improve soil fertility and cabbage (Brassica oleracea var. capitata) productivity - Hao Xia; Muhammad Riaz; Cong Ming; Yuxuan Li; Xiangling Wang; Cuncang Jiang (Journal of Soils and Sediments, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Various beneficial microorganisms colonizing on the surface of biochar primarily originated from the storage environment rather than soil environment - Mengyang Zhang; Hao Xia; Muhammad Riaz; Bo Liu; Zeinab-El-Desouki; Cuncang Jiang (Applied Soil Ecology, 2023)

Improving drought mitigation strategies and disaster risk reduction through MODIS and TRMM-based data in relation to climate change over Pakistan - Shahzad Ali; Abdul Basit; Tyan Alice Makanda; Inamullah; Fahim Ullah Khan; Muhammad Sajid; Tamseela Riaz; Hira Farooq Abbasi; Manzoor; Amir Sohail (Environmental Science and Pollution Research, 2023)

Spatial distribution, compositional profile, sources, ecological and human health risks of legacy and emerging per- and polyfluoroalkyl substances (PFASs) in freshwater reservoirs of Punjab, Pakistan - Rahat Riaz; Muhammad Junaid; Muhammad Yasir Abdur Rehman; Taimoor Iqbal; Jawad Aslam Khan; Yanran Dong; Linxia Yue; Yupeng Chen; Nan Xu; Riffat Naseem Malik (Science of The Total Environment, 2023)

Tracking depositional and geochemical variations in the Cambrian North China Platform: Insights from sedimentology, geochemistry, and C-O isotopic records - Muhammad Riaz; Arman Jafarian; Ardiansyah Koeshidayatullah; Fabrizio Frontalini; Lei Jiang; Khalid Latif; Tehseen Zafar (Sedimentary Geology, 2023)

Cow bone-derived biochar enhances microbial biomass and alters bacterial community composition and diversity in a smelter contaminated soil - Muhammad Azeem; Parimala Gnana Soundari Arockiam Jeyasundar; Amjad Ali; Luqman Riaz; Khalid S. Khan; Qaiser Hussain; Hafiz A. Kareem; Fakhar Abbas; Abdul Latif; Ali Majrashi; Esmat F. Ali; Ronghua Li; et al. (Environmental Research, 2023)

Chemopreventive role of probiotics against cancer: a comprehensive mechanistic review - Shehzeen Noor; Shaukat Ali; Shumaila Riaz; Iqra Sardar; Muhammad Adeel Farooq; Ayesha Sajjad (Molecular Biology Reports, 2023)

Determining satellite-based evapotranspiration product and identifying relationship with other observed data in Punjab, Pakistan - Muhammad Amin; Mobushir Riaz Khan; Sher Shah Hassan; Muhammad Imran; Muhammad Hanif; Irfan Ahmad Baig (Environment, Development and Sustainability, 2023)

Transcriptomics for Drought Stress Mediated by Biological Processes in-relation to Key Regulated Pathways in Gossypium darwinii - Cuilian Xu; Muhammad Kashif Ilyas; Richard Odongo Magwanga; Hejun Lu; M Kashif Riaz Khan; Zhongli Zhou; Yujun Li; Zhengcheng Kuang; Asif Javaid; Danish Ibrar; Abdul Ghafoor; Kunbo Wang; et al. (Molecular Biology Reports, 2022)

Boron-Efficient Sugar Beet (Beta vulgaris L.) Cultivar Improves Tolerance to Boron Deficiency by Improving Leaf Traits - Xin Song; Baiquan Song; Jialu Huo; Muhammad Riaz; Xiangling Wang; Wengong Huang; Shaopeng Zhao (Journal of Soil Science and Plant Nutrition, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

Transition metal-doped SnO2 and graphene oxide (GO) supported nanocomposites as efficient photocatalysts and antibacterial agents - Tauseef Munawar; Muhammad Shahid Nadeem; Faisal Mukhtar; Muhammad Naveed ur Rehman; Muhammad Riaz; Sana Batool; Murtaza Hasan; Faisal Iqbal (Environmental Science and Pollution Research, 2022)

Sensitivity analysis of greenhouse gas emissions at farm level: case study of grain and cash crops - Adnan Abbas; Muhammad Waseem; Riaz Ahmad; Khurshied Ahmed khan; Chengyi Zhao; Jianting Zhu (Environmental Science and Pollution Research, 2022)

P-wave minimum 1D velocity model for central and northern Pakistan - Riaz Ahmed Soomro; Saleem Iqbal; Muhammad Ali Shah; Talat Iqbal (Journal of Seismology, 2022)

Effects of yeast extract on the production of phenylpropanoid metabolites in callus culture of purple basil (Ocimum Basilicum L. var purpurascens) and their in-vitro evaluation for antioxidant potential - Gouhar Zaman; Umar Farooq; Muhammad Naeem Bajwa; Hasnain Jan; Muzamil Shah; Riaz Ahmad; Anisa Andleeb; Samantha Drouet; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Molybdenum Role in Nitrogen Bioavailability of Wheat-Soil System Using the Natural 15N Abundance Technique - Mohamed G. Moussa; Xuecheng Sun; Shaimaa El-Tohory; Abdelkader Mohamed; Muhammad Hamzah Saleem; Muhammad Riaz; Zhihao Dong; Lingzhi He; Chengxiao Hu; Marwa A. Ismael (Journal of Soil Science and Plant Nutrition, 2022)

Expression and characterization of heparinase II with MBP tag from a novel strain, Raoultella NX-TZ-3-15 - Yinyin Li; Yue Lin; Yingzi Jiang; Hafiza Mahreen Mehwish; Muhammad Shahid Riaz Rajoka; Liqing Zhao (Archives of Microbiology, 2022)

Antioxidant, antimicrobial, enzyme inhibition, and cytotoxicity guided investigation of Sideroxylon mascatense (A.DC.) T.D. Penn. leaves extracts - Joham Sarfraz Ali; Naheed Riaz; Abdul Mannan; Muhammad Latif; Muhammad Zia (Natural Product Research, 2022)

Effect of Variation in the Mass Ratio on Vortex-Induced Vibration of a Circular Cylinder in Crossflow Direction at Reynold Number = 104: A Numerical Study Using RANS Model - Muhammad Usman Anwar; Maha M. A. Lashin; Niaz B. Khan; Adnan Munir; Mohammed Jameel; Riaz Muhammad; Kamel Guedri; Ahmed M. Galal (Journal of Marine Science and Engineering, 2022)
This study reports on the numerical analysis of the impact of mass ratio on the Vortex-Induced Vibration (VIV) phenomenon of an elastically rigid cylinder, oscillating freely in a crossflow direction. Reynolds-averaged Navier–Stokes (RANS) equations with (k-ω SST) model were used to analyze the flow behavior, amplitude ratio and vortex shedding patterns. The study was performed at constant Reynold number (Re) = 104 with reduced velocity (Ur) ranging from 2 to 14 and mass ratio (m*) of 2.4 and 11. The mass ratio was defined as the ratio between mass of the vibrating cylinder and mass of the fluid displaced. It was found that increasing the mass ratio from 2.4 to 11 resulted in decrease in amplitude response by 80%, 71% and 31% at initial branch, upper to lower transition region and lower branch, respectively. However, the amplitude in the upper branch decreased only 8% at high mass ratio. The peak amplitude observed in the present study was lower than previous experimental and DES results. However, the RANS k-ω SST well captured the vortex shedding modes of 2S, 2P, P + S, and 2T. In 2S mode, two single pairs of vortices were formed, whereas in 2P mode two pairs were generated in single oscillation. Similarly, P + S meant one pair and one individual vortex; whereas 2T mode meant two triplets of vortices generated in one oscillation. The study concluded that increase in mass ratio results in shortening of the lock-in region and decrease in amplitude response.

Effect of forage to concentrate ratio on growth performance and feeding behavior of Thalli lambs - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Karamo Jatta; Sajjad Khan; Muhammad Riaz; Qamar Bilal; Urooj Anwar; Sibtain Ahmad; Hassan Munir Bajwa; Fahd Rasul (Tropical Animal Health and Production, 2022)

Exploring Regional Profile of Drought History- a New Procedure to Characterize and Evaluate Multi-Scaler Drought Indices Under Spatial Poisson Log-Normal Model - Farman Ali; Zulfiqar Ali; Bing-Zhao Li; Sadia Qamar; Amna Nazeer; Saba Riaz; Muhammad Asif Khan; Rabia Fayyaz; Javeria Nawaz Abbasi (Water Resources Management, 2022)

Genome-wide identification and analysis of the GUB_WAK_bind gene family in Gossypium hirsutum - Yingying Tang; Haodong Chen; Tingting Deng; Yan Chang; Kangtai Sun; Allah Ditta; Muhammad Kashif Riaz Khan; Kai Wang; Baohua Wang (Molecular Biology Reports, 2022)

Genome wide analysis of DWARF27 genes in soybean and functional characterization of GmD27c reveals eminent role of strigolactones in rhizobia interaction and nodulation in Glycine max - Naveed ur Rehman; Farhat Abbas; Muhammad Imran; Intikhab Alam; Muhammad Imran; Ihteram Ullah; Muhammad Riaz; Fahim Ullah Khan (Molecular Biology Reports, 2022)

The aluminum tolerance and detoxification mechanisms in plants; recent advances and prospects - Lei Yan; Muhammad Riaz; Jiayou Liu; Min Yu; Jiang Cuncang (Critical Reviews in Environmental Science and Technology, 2022)

Phyto-mediated photocatalysis: a critical review of in-depth base to reactive radical generation for erythromycin degradation - Aniqa Ashraf; Guijian Liu; Balal Yousaf; Muhammad Arif; Rafay Ahmed; Audil Rashid; Luqman Riaz; Muhammad Saqib Rashid (Environmental Science and Pollution Research, 2022)

The potential role of dietary plant ingredients against mammary cancer: a comprehensive review - Amjad Hussain; Marie-Lise Bourguet-Kondracki; Farhad Hussain; Abdur Rauf; Muhammad Ibrahim; Muhammad Khalid; Hidayat Hussain; Javid Hussain; Iftikhar Ali; Anees Ahmed Khalil; Fahad A. Alhumaydhi; Muhammad Khan; et al. (Critical Reviews in Food Science and Nutrition, 2022)

ICP-MS determination of elemental abundance in traditional medicinal plants commonly used in the Kingdom of Saudi Arabia - Rizwan Ahmad; Heba Shaaban; Sahar Y. Issa; Anwar Alsaad; Majd Alghamdi; Njoud Hamid; Rand Osama; Sara Algarni; Ahmed Mostafa; Abdulmalik M. Alqarni; Mohammed Aldholmi; Muhammad Riaz (Food Additives & Contaminants Part B-Surveillance, 2022)

The Oxidative Damage and Morphological Changes of Sugar Beet (Beta vulgaris L.) Leaves at Seedlings Stage Exposed to Boron Deficiency in Hydroponics - Xin Song; Xueming Hao; Baiquan Song; Xiaoyu Zhao; Zhenzhen Wu; Xiangling Wang; Jiyu Du; Wengong Huang; Muhammad Riaz; Xingfan Li; Jiaxin Li; Meiyu Li; et al. (Sugar Tech, 2022)

In vitro synergy of entomopathogenic fungi and differential-chemistry insecticides against armyworm Spodoptera litura Fabricius (Lepidoptera: Noctuidae) - Zainab Batool; Muhammad Asam Riaz; Samy Sayed; Muhammad Zeeshan Majeed; Sohail Ahmed; Sami Ullah (International Journal of Tropical Insect Science, 2022)

From the COVID-19 pandemic to corrupt practices: a tale of two evils - Muhammad Usman; Mudassir Husnain; Muhammad Waheed Akhtar; Yameen Ali; Areej Riaz; Aimon Riaz (Environmental Science and Pollution Research, 2022)

Addition of Clayey Soil to Sandy Soil Increases Sorption of Water-Extractable Organic C But Also Its Release - Muhammad Riaz; Petra Marschner (Journal of Soil Science and Plant Nutrition, 2022)

Sequence stratigraphy, depositional and diagenetic environments of the late Cambrian glauconite bearing oolitic limestones in the Kelan Section, Shanxi, China - Muhammad Riaz; G M Bhat; Khalid Latif; Tehseen Zafar; Shahid Ghazi (Journal of Earth System Science, 2022)

Effects of bisphenol a on hematological, serum biochemical, and histopathological biomarkers in bighead carp (Aristichthys nobilis) under long-term exposure - Rabia Akram; Rehana Iqbal; Riaz Hussain; Muhammad Ali (Environmental Science and Pollution Research, 2022)

Morphology and genesis of the Cambrian oncoids in Wuhai Section, Inner Mongolia, China - Muhammad Riaz; Khalid Latif; Tehseen Zafar; Enzhao Xiao; Shahid Ghazi (Carbonates and Evaporites, 2022)

Isolation and identification of two new compounds from the seeds of Moringa oleifera and their antiviral and anti-inflammatory activities - Yongai Xiong; Muhammad Shahid Riaz Rajoka; MengXun Zhang; Zhendan He (Natural Product Research, 2022)

A spreadsheet-based tool for optimal design of reinforced concrete cantilever retaining walls - Mansoor Shakeel; Rizwan Azam; Muhammad Rizwan Riaz (Innovative Infrastructure Solutions, 2022)

Mechanical and durability properties of fly-ash cement sand composite bricks: an alternative to conventional burnt clay bricks - Azaz Waheed; Rizwan Azam; Muhammad Rizwan Riaz; Mohamed Zawam (Innovative Infrastructure Solutions, 2022)

Taxonomic implications of leaf epidermis in halophytes of Amaranthaceae from Salt Range of Punjab, Pakistan - Moona Nazish; Mushtaq Ahmad; Riaz Ullah; Abdelaaty A. Shahat; Daniel Potter; Muhammad Zafar; Shazia Sultana (Plant Biosystems, 2022)

Anti-hepatitis C virus and synergistic potential of Syzgium cumine a bioassay guided screening in liver-infected hepatocytes - Sana Riaz; Hira Tiwana; Muhammad Adil; Khaver Ali; Tariq Javed (Archives of Microbiology, 2022)

Impact of water–sediment interaction on hydrogeochemical signature of dug well aquifer by using geospatial and multivariate statistical techniques of Islamkot sub-district, Tharparkar district, Sindh, Pakistan - Muhammad Soomar Samtio; Khadim Hussain Rajper; Asghar Ali alias Daahar Hakro; Muhammad Farooque Lanjwani; Abdul Qayoom Mughari; Rakhshanda Sadaf; Riaz Hussain Rajper; Abdul Shakoor Mastoi; Muhammad Hassan Agheem; Rafique Ahmed Lashari; Taj Muhmmad Jahangir (Arabian Journal of Geosciences, 2022)

Metadherin (MTDH) overexpression significantly correlates with advanced tumor grade and stages among colorectal cancer patients - Aimen Sultan; Namood-E Sahar; Syeda Kiran Riaz; Javeria Qadir; Shahzad Hussain Waqar; Farhan Haq; Tanwir Khaliq; Muhammad Faraz Arshad Malik (Molecular Biology Reports, 2021)

Wetting Induced Deformation of Soils Triggering Landslides in Pakistan - Saima Riaz; Mamoru Kikumoto; Muhammad Basharat; Andius Dasa Putra (Geotechnical and Geological Engineering, 2021)

Prevalence of antibiotic-resistant bacterial strains in wastewater streams: molecular characterization and relative abundance - Marium Fiaz; Iftikhar Ahmed; Rabaila Riaz; Uzma Nawaz; Muhammad Arshad (Folia Microbiologica, 2021)

Ameliorative mechanisms of turmeric-extracted curcumin on arsenic (As)-induced biochemical alterations, oxidative damage, and impaired organ functions in rats - Anam Ishaq; Huma Gulzar; Ali Hassan; Muhammad Kamran; Muhammad Riaz; Aasma Parveen; Muhammad Sohaib Chattha; Noman Walayat; Sana Fatima; Sobia Afzal; Shah Fahad (Environmental Science and Pollution Research, 2021)

Arsenic exposure through drinking groundwater and consuming wastewater-irrigated vegetables in Multan, Pakistan - Mamoona Amir; Salman Asghar; Muhammad Ahsin; Shahid Hussain; Amir Ismail; Muhammad Riaz; Safina Naz (Environmental Geochemistry and Health, 2021)

Implication of Remote Sensing Data under GIS Environment for Appraisal of Irrigation System Performance - Sultan Ahmad Rizvi; Afeef Ahmad; Muhammad Latif; Abdul Sattar Shakir; Aftab Ahmad Khan; Waqas Naseem; Muhammad Riaz Gondal (Water Resources Management, 2021)

First report of Cotton leaf curl Kokhran virus associated with Cotton leaf curl Multan betasatellite infecting soybean in Pakistan - Maddiha Riaz; Muhammad Zubair; Saleem Ur Rahman; Shahid Mansoor (Journal of Plant Pathology, 2021)

Determinants and implications of environmental practices for waste management and the minimization in the construction industry: a case study of Pakistan - Ahsan Riaz Khan; Allah Ditta; Muhammad Sajid Mehmood; Zheng MaoSheng; Maryam Natalia (Environmental Science and Pollution Research, 2021)

Experimental and comparative study of Chinese commercial improved coal-fired cooking and space-heating stoves - Riaz Ahmad; Adnan Abbas; Wang Jufei; Li Hua; Muhammad Sultan; Bohong Li; Samuel M Nyambura; Pan Xingjia (Environmental Science and Pollution Research, 2021)

Preparation and Characterization of pH-Independent Sustained-Release Tablets Containing Hot Melt Extruded Solid Dispersions of Clarithromycin - Qazi Amir Ijaz; Sumera Latif; Qurat-ul-ain Shoaib; Memoona Rashid; Muhammad Sohail Arshad; Amjad Hussain; Nadeem Irfan Bukhari; Sohail Riaz; Nasir Abbas (AAPS PharmSciTech, 2021)

Mitochondrial phylogenetic and diversity analysis in Azi-Kheli buffalo - Farhad Ali; Ijaz Ahmad; Muhammad Ijaz Ali; Muhammad Hasnain Riaz; Nadar Khan; Obaid Ullah; Faizul Hassan; Syed Muhammad Suhail; Rajwali Khan; Muhammad Tahir Khan; Irshad Ahmad; Muhammad Tariq Zeb (Tropical Animal Health and Production, 2021)

Exposure of broiler chickens to chronic heat stress increases the severity of white striping on the pectoralis major muscle - Muhammad Adnan Aslam; Emrah İpek; Roshan Riaz; Şule Yurdagül Ӧzsoy; Waseem Shahzad; Ӧzay Güleş (Tropical Animal Health and Production, 2021)

Antioxidative and Anti-inflammatory Effects of Kojic Acid in Aβ-Induced Mouse Model of Alzheimer’s Disease - Amjad Khan; Tae Ju Park; Muhammad Ikram; Sareer Ahmad; Riaz Ahmad; Min Gi Jo; Myeong Ok Kim (Molecular Neurobiology, 2021)

Occurrence, distribution, and pollution indices of potentially toxic elements within the bed sediments of the riverine system in Pakistan - Javed Nawab; Zia Ud Din; Riaz Ahmad; Sardar Khan; Mazhar Iqbal Zafar; Shah Faisal; Waleed Raziq; Hamza Khan; Zia Ur Rahman; Abid Ali; Muhammad Qayash Khan; Sajid Ullah; et al. (Environmental Science and Pollution Research, 2021)

Distance attenuation and local magnitude scale based on constant geometrical spreading in Northern Punjab, Pakistan - Mohammad Tahir; Ali Khan; Muhammad Naveed Mushtaq; Muhammad Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah; Karam Khan; Riaz Ahmed Soomro (Acta Geophysica, 2021)

Gradient-based impedance synthesis for breast and lung cancer cell screening deploying planar and nano-structured electrodes - Muhammad Awais Aslam; Kashif Riaz; Muhammad Mubasher Saleem (Medical & Biological Engineering & Computing, 2021)

Climate change during the COVID-19 outbreak: scoping future perspectives - Muhammad Usman; Mudassir Husnain; Aimon Riaz; Areej Riaz; Yameen Ali (Environmental Science and Pollution Research, 2021)

A review of landslides related to the 2005 Kashmir Earthquake: implication and future challenges - Muhammad Basharat; Muhammad Tayyib Riaz; M. Qasim Jan; Chong Xu; Saima Riaz (Natural Hazards, 2021)

Sunlight-induced photocatalytic degradation of various dyes and bacterial inactivation using CuO–MgO–ZnO nanocomposite - Tauseef Munawar; Faisal Mukhtar; Sadaf Yasmeen; Muhammad Naveed-ur-Rehman; Muhammad Shahid Nadeem; Muhammad Riaz; Muhammad Mansoor; Faisal Iqbal (Environmental Science and Pollution Research, 2021)

Isolation and functional characterization of exopolysaccharide produced by Lactobacillus plantarum S123 isolated from traditional Chinese cheese - Muhammad Saleem; Samiullah Malik; Hafiza Mahreen Mehwish; Muhammad Waqas Ali; Nazim Hussain; Mohsin Khurshid; Muhammad Shahid Riaz Rajoka; Yougen Chen (Archives of Microbiology, 2021)

Occupational health impacts of transport industry: collagen degrader, blood lead, and respiratory illnesses - Waheed Anjum; Nadia Riaz; Muhammad Saqib; Malik Tahir Hayat; Zahid Ullah; Qaisar Mahmood (Arabian Journal of Geosciences, 2021)

Role of sea-level pressure of Arabian Sea on variability of summer monsoon rainfall over Northern Pakistan - Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal; Muhammad Adeel (Theoretical and Applied Climatology, 2021)

Metal accumulation potential, human health risks, and yield attributes of hundred bread wheat genotypes on irrigation with municipal and remediated wastewater - Said Akbar; Zeshan Ali; Sadam Hussain; Ashiq Mohammad; Yousaf Riaz; Adnan Shakeel; Ijaz Ahmad; Maria Mussarat; Riffat Naseem Malik; Kiran Yasmin Khan; Muhammad Sohail; Umar Masood Quraishi (Environmental Science and Pollution Research, 2021)

Expression profiling of miRNA-196a biomarker in naïve hepatitis C virus-infected and Sofosbuvir plus Daclatasvir-treated patients - Nazim Hussain; Nimrah Farooq; Muhammad Maqsood; Muhammad Shahid Riaz Rajoka; Muhammad Bilal (Archives of Microbiology, 2021)

Innovative initiative for effective operation and monitoring using HEC‐RAS modelling of Hakra Branch Canal System, Pakistan * - Muhammad Kamran; Wasif Yousaf; R.L.H.L. Rajapakse; Wakas Kareem Awan; Muhammad Riaz; Nayyar Minhaj Asif; Muhammad Umar; Usman Tehsin Shah (Irrigation and Drainage, 2021)
The Punjab Irrigation System is one of the world's largest contiguous systems, with its entire network extending over nearly 31,000 km in length. The system faces numerous constraints that limit the canal operations and their respective design discharges. Shortage of irrigation water is a contest that normally occurs at canal tail‐end users. The hydraulic performance of open canal networks is not easy to assess; therefore, it is impossible to feed the lateral offtakes with their design shares without changing designed or existing gate openings. To overcome these problems, a Hydrologic Engineering Center's River Analysis System (HEC‐RAS) model has been developed to simulate the flow situation in the canal system. For this study, the Hakra Branch Canal System with a command area of 1.4 million hectares was selected. To recognize model performance, water levels at the head of the canal and tail discharge have been compared with field data. The simulated results show the best‐fit match with field head water levels with coefficients of determination ( R 2 ) of 0.765 and 0.877 and tail discharges of the canal with R 2 = 0.707 and 0.945, for calibration and validation periods, respectively. The hydraulic simulation model is a useful tool for effective canal operation to determine the losses and find out the expected discharge for the tail‐end users. It has been observed that the proportion of excess actual delivery of water to lateral offtakes results in inadequate water supply for the tail‐end users. It is recommended that during the observation of the seasonally discharge table, the irrigation engineer should adjust a factor either in the HEC‐RAS model or in the observed data. It is also recommended to develop an unsteady model for considering sediment transport.

Geotechnical investigation and landslide susceptibility assessment along the Neelum road: a case study from Lesser Himalayas, Pakistan - Khawaja Shoaib Ahmed; Muhammad Basharat; Muhammad Tayyib Riaz; Yasir Sarfraz; Amir Shahzad (Arabian Journal of Geosciences, 2021)

Landfill site selection by integrating fuzzy logic, AHP, and WLC method based on multi-criteria decision analysis - Riaz Zarin; Muhammad Azmat; Salman Raza Naqvi; Qaisar Saddique; Saif Ullah (Environmental Science and Pollution Research, 2021)

Role of silicon on root morphological characters of wheat (Triticum aestivum L.) plants grown under Cd-contaminated nutrient solution - Shafeeq Ur Rahman; Qi Xuebin; Ghulam Yasin; Hefa Cheng; Faisal Mehmood; Muhammad Zain; Muhammad Shehzad; Muhammad Irfan Ahmad; Luqman Riaz; Abdur Rahim; Saeed Ur Rahman (Acta Physiologiae Plantarum, 2021)

Impact of light stimulation during incubation on hatching traits and post-hatch performance of commercial broilers - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Abd ur Rehman; Muhammad Usman; Shahid Mehmood; Sohail Ahmad (Tropical Animal Health and Production, 2021)

Biochar and leguminous cover crops as an alternative to summer fallowing for soil organic carbon and nutrient management in the wheat-maize-wheat cropping system under semiarid climate - Muhammad Arif; Ikramullah; Talha Jan; Muhammad Riaz; Kashif Akhtar; Salman Ali; Shahen Shah; Fazal Jalal; Ishaq A. Mian; Khadim Muhammad Dawar; Haiyan Wang (Journal of Soils and Sediments, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Molybdenum supply increases root system growth of winter wheat by enhancing nitric oxide accumulation and expression of NRT genes - Muhammad Imran; Xuecheng Sun; Saddam Hussain; Muhammad Shoaib Rana; Muhammad Hamzah Saleem; Muhammad Riaz; Xiangru Tang; Imran Khan; Chengxiao Hu (Plant and Soil, 2021)

Nexus between green finance and climate change mitigation in N-11 and BRICS countries: empirical estimation through difference in differences (DID) approach - Muhammad Atif Nawaz; Usha Seshadri; Pranav Kumar; Ramaisa Aqdas; Ataul Karim Patwary; Madiha Riaz (Environmental Science and Pollution Research, 2021)

Higher biochar rate strongly reduced decomposition of soil organic matter to enhance C and N sequestration in nutrient-poor alkaline calcareous soil - Samar Fatima; Muhammad Riaz; Mohammad I. Al-Wabel; Muhammad Saleem Arif; Tahira Yasmeen; Qaiser Hussain; Mahnaz Roohi; Shah Fahad; Kawsar Ali; Muhammad Arif (Journal of Soils and Sediments, 2021)

Interactive role of zinc and iron lysine on Spinacia oleracea L. growth, photosynthesis and antioxidant capacity irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Hamzah Saleem; Mohsin Ali; Muhammad Riaz; Sehar Javed; Anam Sehar; Zohaib Abbas; Muhammad Rizwan; Mohamed A. El-Sheikh; Mohammed Nasser Alyemeni (Physiology and Molecular Biology of Plants, 2020)

Sandy Soil Amended with Clay Soil: Effect of Clay Soil Properties on Soil Respiration, Microbial Biomass, and Water Extractable Organic C - Muhammad Riaz; Petra Marschner (Journal of Soil Science and Plant Nutrition, 2020)

Dechlorane Plus as an emerging environmental pollutant in Asia: a review - Mazhar Iqbal Zafar; Sundas Kali; Mehtabidah Ali; Muhammad Asam Riaz; Tayyaba Naz; Muhammad Mazhar Iqbal; Noshin Masood; Kashif Munawar; Bilal Jan; Sohail Ahmed; Amir Waseem; Muhammad Bilal Khan Niazi (Environmental Science and Pollution Research, 2020)

Exploring the potential of Sentinel-2A satellite data for aboveground biomass estimation in fragmented Himalayan subtropical pine forest - Mobiishir Riaz Khan; Iftikhar Ahmad Khan; Muhammad Hasan Ali Baig; Zheng-jia Liu; Muhammad Irfan Ashraf (Journal of Mountain Science, 2020)

The potential and efficacy of Allium sativum leaf lectin (ASAL) against sap-sucking insect pests of transgenic maize - Muhammad Umar Bhatti; Saman Riaz; Nida Toufiq; Olawale Samuel Adeyinka; Anwar Khan; Iqra Yousaf; Muhammad Tariq; Shahid Murtaza; Idrees Ahmad Nasir; Bushra Tabassum (Biologia, 2020)

Exogenous calcium mitigates heat stress effects in common bean: a coordinated impact of photoprotection of PSII, up-regulating antioxidants, and carbohydrate metabolism - Muhammad Naeem; Jesse Riaz Traub; Habib-ur-Rehman Athar; Wayne Loescher (Acta Physiologiae Plantarum, 2020)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Identification of significant risks in pediatric acute lymphoblastic leukemia (ALL) through machine learning (ML) approach - Nasir Mahmood; Saman Shahid; Taimur Bakhshi; Sehar Riaz; Hafiz Ghufran; Muhammad Yaqoob (Medical & Biological Engineering & Computing, 2020)

Influence of metallic species for efficient photocatalytic water disinfection: bactericidal mechanism of in vitro results using docking simulation - Aaima Iftikhar; Muhammad Saqib Khan; Umer Rashid; Qaisar Mahmood; Habiba Zafar; Muhammad Bilal; Nadia Riaz (Environmental Science and Pollution Research, 2020)

Comparative efficacy of mitigation techniques for the detoxification of Prunus persica (L.) from selected pesticide residues - Neelab; Muhammad Rafique Asi; Sundas Kali; Muhammad Asam Riaz; Amir Waseem; Muhammad Mazhar Iqbal; Nauman Ahmad; Mazhar Iqbal; Noshin Masood; Mazhar Iqbal Zafar (Environmental Science and Pollution Research, 2020)

Chemical fractionation and risk assessment of trace elements in sewage sludge generated from various states of Pakistan - Umair Riaz; Ghulam Murtaza; Saifullah; Muhammad Farooq; Humera Aziz; Ayesha Abdul Qadir; Shahzada Munawar Mehdi; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Developing the first halophytic turfgrasses for the urban landscape from native Arabian desert grass - Muhammad Zamin; Shah Fahad; Abdul Mateen Khattak; Muhammad Adnan; Fazli Wahid; Ahmad Raza; Depeng Wang; Shah Saud; Muhammad Noor; Hafiz Faiq Bakhat; Muhammad Mubeen; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2020)

Correction to: Contribution to the comparative study of treated and untreated wastewater: a case study (Wadi Fatima and Al Misk Lake) in Saudi Arabia - Faisal Rehman; Ali M. Subyani; Tariq Cheema; Hussein M. Harbi; Tahir Azeem; Abbas Ali Naseem; Faisal Rehman; Muhammad Fahad Ullah; Omar Riaz; Saif ur Rehman (Arabian Journal of Geosciences, 2020)

Reproductive tissues-specific meta-QTLs and candidate genes for development of heat-tolerant rice cultivars - Qasim Raza; Awais Riaz; Khurram Bashir; Muhammad Sabar (Plant Molecular Biology, 2020)

Petrographic and rare earth elemental characteristics of Cambrian Girvanella oncoids exposed in the North China Platform: Constraints on forming mechanism, REE sources, and paleoenvironments - Muhammad Riaz; Tehseen Zafar; Khalid Latif; Shahid Ghazi; Enzhao Xiao (Arabian Journal of Geosciences, 2020)

Contribution to the comparative study of treated and untreated wastewater: a case study (Wadi Fatima and Al Misk Lake) in Saudi Arabia - Faisal Rehman; Ali M. Subyani; Tariq Cheema; Hussein M. Harbi; Tahir Azeem; Abbas Ali Naseem; Faisal Rehman; Muhammad Fahad Ullah; Omar Riaz; Saif ur Rehman (Arabian Journal of Geosciences, 2020)

Advances in exogenous RNA delivery techniques for RNAi-mediated pest control - Olawale Samuel Adeyinka; Saman Riaz; Nida Toufiq; Iqra Yousaf; Muhammad Umar Bhatti; Anicet Batcho; Amos Afolarin Olajide; Idrees Ahmad Nasir; Bushra Tabassum (Molecular Biology Reports, 2020)

The impact of airborne pollution and exposure to solar ultraviolet radiation on skin: mechanistic and physiological insight - Atif Ali; Hira Khan; Raheem Bahadar; Asma Riaz; Muhammad Hassham Hassan Bin Asad (Environmental Science and Pollution Research, 2020)

Re-examining log law velocity profile in smooth open channel flows - Nadeeka S. Miguntanna; Hamish Moses; Muttucumaru Sivakumar; Shu-Qing Yang; Keith James Enever; Muhammad Zain Bin Riaz (Environmental Fluid Mechanics, 2020)

Distribution and Mobility of Foliar-Applied Boron (10B) in Citrange Rootstock Under Different Boron Conditions - Xiuwen Wu; Muhammad Riaz; Lei Yan; Cuncang Jiang (Journal of Plant Growth Regulation, 2020)

Resistance to Chilo infuscatellus (Lepidoptera: Pyraloidea) in transgenic lines of sugarcane expressing Bacillus thuringiensis derived Vip3A protein - Saman Riaz; Idrees Ahmad Nasir; Muhammad Umar Bhatti; Olawale Samuel Adeyinka; Nida Toufiq; Iqra Yousaf; Bushra Tabassum (Molecular Biology Reports, 2020)

Regeneration response of carnation cultivars in response of silver nanoparticles under in vitro conditions - Muhammad Zia; Kamran Yaqoob; Abdul Mannan; Sobia Nisa; Ghulam Raza; Riaz ur Rehman (Vegetos, 2020)

Ameliorative Effects of Biochar on Rapeseed (Brassica napus L.) Growth and Heavy Metal Immobilization in Soil Irrigated with Untreated Wastewater - Muhammad Kamran; Zaffar Malik; Aasma Parveen; Li Huang; Muhammad Riaz; Saqib Bashir; Adnan Mustafa; Ghulam Hassan Abbasi; Bin Xue; Umeed Ali (Journal of Plant Growth Regulation, 2020)

Nanozymes for medical biotechnology and its potential applications in biosensing and nanotherapeutics - Samman Munir; Asad Ali Shah; Hazir Rahman; Muhammad Bilal; Muhammad Shahid Riaz Rajoka; Abdul Arif Khan; Mohsin Khurshid (Biotechnology Letters, 2020)

Awareness and current knowledge of epilepsy - Asmat Ullah Khan; Muhammad Akram; Muhammad Daniyal; Naheed Akhter; Muhammad Riaz; Naheed Akhtar; Mohammad Ali Shariati; Fozia Anjum; Samreen Gul Khan; Abida Parveen; Saeed Ahmad (Metabolic Brain Disease, 2020)

Photocatalytic degradation and kinetic modeling of azo dye using bimetallic photocatalysts: effect of synthesis and operational parameters - Nadia Riaz; Maryam Hassan; Maria Siddique; Qaisar Mahmood; Umar Farooq; Rizwana Sarwar; Muhammad Saqib Khan (Environmental Science and Pollution Research, 2020)

Correction to: Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Characterization, the Antioxidant and Antimicrobial Activity of Exopolysaccharide Isolated from Poultry Origin Lactobacilli - Muhammad Shahid Riaz Rajoka; Hafiza Mahreen Mehwish; Hafiz Fakhar Hayat; Nazim Hussain; Sobia Sarwar; Humaira Aslam; Ahmad Nadeem; Junling Shi (Probiotics and Antimicrobial Proteins, 2019)

Mercury Contamination in Water and Sediments and the Associated Health Risk: A Case Study of Artisanal Gold-mining - Arjumand Riaz; Sardar Khan; Said Muhammad; Mohammad Tahir Shah (Mine Water and the Environment, 2019)

First detection and molecular characterization of avian polyomavirus in young parrots in Pakistan - Aayesha Riaz; Arfan Yousaf; Muhammad Moaeen-ud-Din; Muhammad Ali Abdullah Shah; Tayyaba Zainab; Sadia Masood; Naeem Akhter; Adnan Ali (Veterinary Research Communications, 2019)

Experimental investigation of a catastrophic landslide in northern Pakistan - Saima Riaz; Gonghui Wang; Muhammad Basharat; Kaoru Takara (Landslides, 2019)

Metal-induced nephrotoxicity to diabetic and non-diabetic Wistar rats - Muhammad Ahsan Riaz; Zaib Un Nisa; Azra Mehmood; Muhammad Sohail Anjum; Khurram Shahzad (Environmental Science and Pollution Research, 2019)

Calcified cyanobacteria fossils from the leiolitic bioherm in the Furongian Changshan Formation, Datong (North China Platform) - Khalid Latif; Enzhao Xiao; Muhammad Riaz; Abdullah Ali Ali Hussein (Carbonates and Evaporites, 2019)

Inhibitory effects of Clematis orientalis aqueous ethanol extract and fractions on inflammatory markers in complete Freund's adjuvant-induced arthritis in Sprague–Dawley rats - Umme Habiba Hasan; Alamgeer; Muhammad Shahzad; Shah Jahan; Zahid Rasul Niazi; Ishfaq Ali Bukhari; Asaad Mohamed Assiri; Hamayun Riaz (Inflammopharmacology, 2019)

Health risk assessment of drinking arsenic-containing groundwater in Hasilpur, Pakistan: effect of sampling area, depth, and source - Riaz Ahmad Tabassum; Muhammad Shahid; Camille Dumat; Nabeel Khan Niazi; Sana Khalid; Noor Samad Shah; Muhammad Imran; Samina Khalid (Environmental Science and Pollution Research, 2019)

Over 100 years of faults interaction, stress accumulation, and creeping implications, on Chaman Fault System, Pakistan - Muhammad Shahid Riaz; Shan Bin; Shahid Naeem; Wang Kai; Zujun Xie; Syed Mushhad M. Gilani; Umer Ashraf (International Journal of Earth Sciences, 2019)

Influence of different organic geo-sorbents on Spinacia oleracea grown in chromite mine-degraded soil: a greenhouse study - Javed Nawab; Nayab Khan; Riaz Ahmed; Sardar Khan; Junaid Ghani; Ziaur Rahman; Fawad Khan; Xiaoping Wang; Juma Muhammad; Hassan Sher (Journal of Soils and Sediments, 2019)

Occurrence of Aflatoxin M1 in raw and processed milk and assessment of daily intake in Lahore, Multan cities of Pakistan - Mateen Ahmad; Muhammad Awais; Shinawar Waseem Ali; Hafiz Azhar Ali Khan; Muhammad Riaz; Asif Sultan; Muhammad Shakeel Bashir; Adnan Ishtiaq Chaudhry (Food Additives & Contaminants Part B-Surveillance, 2019)

Metabolic changes in roots of trifoliate orange [Poncirus trifoliate (L.) Raf.] as induced by different treatments of boron deficiency and resupply - Xiuwen Wu; Guidong Liu; Muhammad Riaz; Lei Yan; Cuncang Jiang (Plant and Soil, 2019)

Arsenic Level and Risk Assessment of Groundwater in Vehari, Punjab Province, Pakistan - Muhammad Shahid; Muhammad Khalid; Camille Dumat; Sana Khalid; Nabeel Khan Niazi; Muhammad Imran; Irshad Bibi; Iftikhar Ahmad; Hafiz Mohkum Hammad; Riaz Ahmad Tabassum (Exposure and Health, 2018)

Sugarcane waste straw biochar and its effects on calcareous soil and agronomic traits of okra - Muhammad Riaz; Mumtaz Khan; Shafaqat Ali; Muhammad Daud Khan; Rehan Ahmad; Muhammad Jamil Khan; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Synthesis, in vitro $$α $$ α -glucosidase inhibitory activity, and in silico study of (E)-thiosemicarbazones and (E)-2-(2-(arylmethylene)hydrazinyl)-4-arylthiazole derivatives - Muhammad Ali; Khalid Mohammed Khan; Uzma Salar; Mohammed Ashraf; Muhammad Taha; Abdul Wadood; Sujhla Hamid; Muhammad Riaz; Basharat Ali; Shahbaz Shamim; Farman Ali; Shahnaz Perveen (Molecular Diversity, 2018)

Regolith thickness modeling using a GIS approach for landslide distribution analysis, NW Himalayas - Muhammad Basharat; Masood Qasim; Muhammad Shafique; Nasir Hameed; Muhammad Tayyib Riaz; Muhammad Rustam Khan (Journal of Mountain Science, 2018)

Coal mining trends, approaches, and safety hazards: a brief review - Muhammad Fahad Ullah; Abdullah M. Alamri; Khalid Mehmood; Mian Sohail Akram; Faisal Rehman; Saif Ur Rehman; Omar Riaz (Arabian Journal of Geosciences, 2018)

Strategic use of water: a step toward cadmium-free basmati rice (Oryza sativa L.) - Muhammad Naveed; Saifullah; Umair Riaz; Ghulam Murtaza; Sadia Bibi; Ammara Arooj; Qamar uz Zaman (Paddy and Water Environment, 2018)

Terminal drought and seed priming improves drought tolerance in wheat - Tahira Tabassum; Muhammad Farooq; Riaz Ahmad; Ali Zohaib; Abdul Wahid; Muhammad Shahid (Physiology and Molecular Biology of Plants, 2018)

Influence of Siberian High on temperature variability over northern areas of South Asia - Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal; Mirza Jawwad Baig (Meteorology and Atmospheric Physics, 2018)

Monitoring and spatiotemporal variations of pyrethroid insecticides in surface water, sediment, and fish of the river Chenab Pakistan - Ghazala Riaz; Amtul Bari Tabinda; Muhammad Kashif; Abdullah Yasar; Adeel Mahmood; Rizwan Rasheed; Muhammad Imran Khan; Javed Iqbal; Sidra Siddique; Yusra Mahfooz (Environmental Science and Pollution Research, 2018)

Effects of anthropogenic nitrogen deposition on soil nitrogen mineralization and immobilization in grassland soil under semiarid climatic conditions - Ambreen Bhatti; Jawad Ahmad; Muhammad Qasim; Muhammad Riaz; Malcolm S. Cresser (Environmental Monitoring and Assessment, 2018)

A critical review of mechanisms involved in the adsorption of organic and inorganic contaminants through biochar - Zohaib Abbas; Shafaqat Ali; Muhammad Rizwan; Ihsan Elahi Zaheer; Afifa Malik; Muhammad Ahsan Riaz; Muhammad Rizwan Shahid; Muhammad Zia ur Rehman; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Analysis of the resistance of Gossypium herbaceum to cotton leaf curl kokhran virus strain burewala and cotton leaf curl multan betasatellite - Rahim Ullah; Khalid Pervaiz Akhtar; Peter Moffett; Tawaf Ali Shah; Manzoor Hussain; Muhammad Kashif Riaz Khan; Shahid Mansoor; Muhammad Saeed (Journal of Plant Pathology, 2018)

Effect of foliar-applied iron complexed with lysine on growth and cadmium (Cd) uptake in rice under Cd stress - Arooj Bashir; Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Wajid Ishaque; Muhammad Atif Riaz; Arosha Maqbool (Environmental Science and Pollution Research, 2018)

Correction to: Increasing water productivity, nitrogen economy, and grain yield of rice by water saving irrigation and fertilizer-N management - Omar Aziz; Saddam Hussain; Muhammad Rizwan; Muhammad Riaz; Saqib Bashir; Lirong Lin; Sajid Mehmood; Muhammad Imran; Rizwan Yaseen; Guoan Lu (Environmental Science and Pollution Research, 2018)

Increasing water productivity, nitrogen economy, and grain yield of rice by water saving irrigation and fertilizer-N management - Omar Aziz; Saddam Hussain; Muhammad Rizwan; Muhammad Riaz; Saqib Bashir; Lirong Lin; Sajid Mehmood; Muhammad Imran; Rizwan Yaseen; Guoan Lu (Environmental Science and Pollution Research, 2018)

Mercury contamination in selected foodstuffs and potential health risk assessment along the artisanal gold mining, Gilgit-Baltistan, Pakistan - Arjumand Riaz; Sardar Khan; Said Muhammad; Caihong Liu; Mohammad Tahir Shah; Mohsin Tariq (Environmental Geochemistry and Health, 2018)

Sugarcane bagasse-derived biochar reduces the cadmium and chromium bioavailability to mash bean and enhances the microbial activity in contaminated soil - Saqib Bashir; Qaiser Hussain; Muhammad Akmal; Muhammad Riaz; Hongqing Hu; Shahzada Sohail Ijaz; Muhammad Iqbal; Shaukat Abro; Sajid Mehmood; Munir Ahmad (Journal of Soils and Sediments, 2018)

PAAN135, a novel rhizospheric fungus associated with Cholistan desert grass Panicum antidotale, is a species of Saccharomycetales and a new source of cyclo-L-prolylglycine diketopiperazine - Faiz-ul-Hassan Nasim; Adeela Naureen; Muhammad Saleem; Naheed Riaz; Muhammad Shafiq Choudhary; Muhammad Ashraf (Symbiosis, 2018)

Interaction of boron and aluminum on the physiological characteristics of rape (Brassica napus L.) seedlings - Lei Yan; Muhammad Riaz; Xiuwen Wu; Yuhan Wang; Chenqing Du; Cuncang Jiang (Acta Physiologiae Plantarum, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

3D graphene-based nanostructured materials as sorbents for cleaning oil spills and for the removal of dyes and miscellaneous pollutants present in water - Muhammad Adil Riaz; Gordon McKay; Junaid Saleem (Environmental Science and Pollution Research, 2017)

Singular value decomposition analysis for examining the impact of Siberian High on winter precipitation variability over South Asia - Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal (Theoretical and Applied Climatology, 2017)

Seasonality in hospital admissions of Crimean-Congo hemorrhagic fever and its dependence on ambient temperature—empirical evidence from Pakistan - Tariq Abbas; Zhiwei Xu; Muhammad Younus; Abdul Qayyum; Muhammad T. Riaz (International Journal of Biometeorology, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Genes responsible for powdery mildew resistance and improvement in wheat using molecular marker-assisted selection - Liaqat Shah; Shamsur Rehman; Asif Ali; Muhammad Yahya; Muhammad Waheed Riaz; Hongqi Si; Chuanxi Ma; Jie Lu (Journal of Plant Diseases and Protection, 2017)

Wheat productivity responses in the rice-based system under different no-till techniques and nitrogen sources - Muhammad Hamid Rafiq; Riaz Ahmad; Abdul Jabbar; Hassan Munir; Muzzammil Hussain (Environmental Science and Pollution Research, 2017)

Water-saving technologies affect the grain characteristics and recovery of fine-grain rice cultivars in semi-arid environment - Khawar Jabran; Muhammad Riaz; Mubshar Hussain; Wajid Nasim; Umar Zaman; Shah Fahad; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Biochar soil amendment on alleviation of drought and salt stress in plants: a critical review - Shafaqat Ali; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Ibrahim; Muhammad Riaz; Muhammad Saleem Arif; Farhan Hafeez; Mohammad I. Al-Wabel; Ahmad Naeem Shahzad (Environmental Science and Pollution Research, 2017)

Natural products from Cuscuta reflexa Roxb . with antiproliferation activities in HCT116 colorectal cell lines - Muhammad Riaz; Aishah Bilal; Muhammad Shaiq Ali; Itrat Fatima; Amir Faisal; Muhammad Azhar Sherkheli; Adnan Asghar (Natural Product Research, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

Prospective study of avian influenza H9 infection in commercial poultry farms of Punjab Province and Islamabad Capital Territory, Pakistan - Mamoona Chaudhry; Maqbool Ahmad; Hamad Bin Rashid; Bakhat Sultan; Haroon Rashid Chaudhry; Aayesha Riaz; Muhammad Shabir Shaheen (Tropical Animal Health and Production, 2017)

Metamorphic temperature investigation of coexisting calcite and dolomite marble––examples from Nikani Ghar marble and Nowshera Formation, Peshawar Basin, Pakistan - Muhammad Fahad; Yaseen Iqbal; Mohammad Riaz; Rick Ubic; Simon A. T. Redfern (Journal of Earth Science, 2016)

Syntheses, in vitro evaluation and molecular docking studies of 5-bromo-2-aryl benzimidazoles as α-glucosidase inhibitors - Tanzila Arshad; Khalid Mohammed Khan; Najma Rasool; Uzma Salar; Shafqat Hussain; Tehreem Tahir; Mohammed Ashraf; Abdul Wadood; Muhammad Riaz; Shahnaz Perveen; Muhammad Taha; Nor Hadiani Ismail (Medicinal Chemistry Research, 2016)

New lipoxygenase and cholinesterase inhibitory sphingolipids from Carthamus oxyacantha - Muhammad Dilshad; Naheed Riaz; Muhammad Saleem; Nusrat Shafiq; Muhammad Ashraf; Tayaba Ismail; Hafiza Mehwish Rafiq; Abdul Jabbar (Natural Product Research, 2016)

A New Broad-Spectrum Peptide Antibiotic Produced by Bacillus brevis Strain MH9 Isolated from Margalla Hills of Islamabad, Pakistan - Syed Aun Muhammad; Amjad Ali; Anam Naz; Afreenish Hassan; Naeem Riaz; Syed Saeed-ul-Hassan; Saadia Andleeb; Debmalya Barh (International Journal of Peptide Research and Therapeutics, 2016)

QTL mapping for salt tolerance at seedling stage in the interspecific cross of Gossypium tomentosum with Gossypium hirsutum - George Oluoch; Juyun Zheng; Xingxing Wang; Muhammad Kashif Riaz Khan; Zhongli Zhou; Xiaoyan Cai; Chunying Wang; Yuhong Wang; Xueyuan Li; Heng Wang; Fang Liu; Kunbo Wang (Euphytica, 2016)

Phytochemistry of Daphne oleoides - Muhammad Riaz; Asma Saleem; Shabana Siddique; Bilal Ahmad Khan; Mohammad Nur-e-Alam; Syed Shahzad-ul-Hussan; Ghulam Abbas Miana; Muhammad Qayyum Khan (Natural Product Research, 2016)

Contrasting effects of untreated textile wastewater onto the soil available nitrogen-phosphorus and enzymatic activities in aridisol - Muhammad Saleem Arif; Muhammad Riaz; Sher Muhammad Shahzad; Tahira Yasmeen; Alexandre Buttler; Juan Carlos Garcıa-Gil; Mahnaz Roohi; Akhtar Rasool (Environmental Monitoring and Assessment, 2016)

Copper-resistant bacteria reduces oxidative stress and uptake of copper in lentil plants: potential for bacterial bioremediation - Faisal Islam; Tahira Yasmeen; Qasim Ali; Muhammad Mubin; Shafaqat Ali; Muhammad Saleem Arif; Sabir Hussain; Muhammad Riaz; Farhat Abbas (Environmental Science and Pollution Research, 2016)

Spatial distribution of pollutant emissions from crop residue burning in the Punjab and Sindh provinces of Pakistan: uncertainties and challenges - Muhammad Irfan; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Sabir Hussain; Muhammad Javed Akhtar; Leon van den Berg; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Estimated daily intake and health risk of heavy metals by consumption of milk - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Zulfiqar Ahmad; Muhammad Saad Hashmi (Food Additives & Contaminants Part B-Surveillance, 2015)

Characterization of N2O emission and associated bacterial communities from the gut of wood-feeding termite Nasutitermes voeltzkowi - Muhammad Zeeshan Majeed; Edouard Miambi; Muhammad Asam Riaz; Alain Brauman (Folia Microbiologica, 2015)

Crossability among modern roses and heterosis of quantitative and qualitative traits in hybrids - Muhammad Nadeem; Adnan Younis; Atif Riaz; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2015)

Pre-planting exogenous application of gibberellic acid influences sprouting, vegetative growth, flowering, and subsequent bulb characteristics of ‘Ad-Rem’ tulip - Fahad Ramzan; Adnan Younis; Atif Riaz; Sajid Ali; Muhammad Irfan Siddique; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2014)

Heavy metals in vegetables and respective soils irrigated by canal, municipal waste and tube well waters - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Mamoona Amir; Muhammad Zafar-ul-Hye (Food Additives & Contaminants Part B-Surveillance, 2014)

Population dynamics of citrus leaf miner on different varieties of citrus in correlation with abiotic environmental factors in Sargodha District, Punjab, Pakistan - Irfan Mustafa; Muhammad Arshad; Abdul Ghani; Iftikhar Ahmad; Abu Bakar Muhammad Raza; Farzana Saddique; Saira Asif; Mobushir Riaz Khan; Haroon Ahmed (Phytoparasitica, 2014)

In vitro propagation of Caralluma tuberculata and evaluation of antioxidant potential - Riaz Ur Rehman; Muhammad Fayyaz Chaudhary; Khalid Mahmood Khawar; Gang Lu; Abdul Mannan; Muhammad Zia (Biologia, 2014)

Interactions of ketoamide inhibitors on HCV NS3/4A protease target: molecular docking studies - Abdul Wadood; Muhammad Riaz; Syed Babar Jamal; Masaud Shah (Molecular Biology Reports, 2014)

Co-inoculation integrated with P-enriched compost improved nodulation and growth of Chickpea (Cicer arietinum L.) under irrigated and rainfed farming systems - Sher Muhammad Shahzad; Azeem Khalid; Muhammad Saleem Arif; Muhammad Riaz; Muhammad Ashraf; Zafar Iqbal; Tahira Yasmeen (Biology and Fertility of Soils, 2014)

Interactive effect of cobalt and nitrogen on growth, nodulation, yield and protein content of field grown pea - Fahmida Mir Akbar; Mohsin Zafar; Abdul Hamid; Maqsood Ahmed; Abdul Khaliq; Muhammad Riaz Khan; Zahid ur Rehman (Horticulture, Environment, and Biotechnology, 2013)

Risks factors associated with subclinical mastitis in water buffaloes in Pakistan - Riaz Hussain; Muhammad Tariq Javed; Ahrar Khan; Ghulam Muhammad (Tropical Animal Health and Production, 2013)

SLC26A4 Mutations in Patients with Moderate to Severe Hearing Loss - Muhammad Riaz Khan; Rasheeda Bashir; Sadaf Naz (Biochemical Genetics, 2013)

Ranging and foraging of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan - Riaz Aziz Minhas; Usman Ali; Muhammad Siddique Awan; Khawaja Basharat Ahmed; Muhammad Nasim Khan; Naeem Iftikhar Dar; Qamar Zaman Qamar; Hassan Ali; Cyril C. Grueter; Yamato Tsuji (Primates, 2013)

Microsatellite analysis of Rosa damascena from Pakistan and Iran - Amjad Farooq; Mahnaz Kiani; Muhammad Aslam Khan; Atif Riaz; Asif Ali Khan; Natalie Anderson; David H. Byrne (Horticulture, Environment, and Biotechnology, 2013)

Antioxidant and lipoxygenase inhibiting new iridoid glucosides from Caryopteris odorata - Tayyaba Shahzadi; Muhammad Athar Abbasi; Aziz Ur-Rehman; Tauheeda Riaz; Khalid Mohammed Khan; Muhammad Ashraf; Iftikhar Afzal; Muhammad Nadeem Akhtar; Muhammad Ajaib (Natural Product Research, 2013)

Application and Opportunities of Pulses in Food System: A Review - Muhammad Asif; Lloyd W. Rooney; Rashida Ali; Mian N. Riaz (Critical Reviews in Food Science and Nutrition, 2013)

NutriTRAILomics in prostate cancer: time to have two strings to one’s bow - Ammad Ahmad Farooqi; Aamir Rana; Asma M. Riaz; Ammara Khan; Muhammad Ali; Sara Javed; Shahzeray Mukhtar; Sehrish Minhaj; Javeria Rafique Rao; Javairia Rajpoot; Rafia Amber; Fiza Asif Javed; et al. (Molecular Biology Reports, 2012)

Extraction, Cleanup, and Chromatographic Determination of Imidacloprid Residues in Wheat - Sajid Iqbal; Riaz Uddin; Sumayya Saied; Mubarik Ahmed; Muhammad Abbas; Sahar Aman (Bulletin of Environmental Contamination and Toxicology, 2012)

Carnivore diet analysis based on next‐generation sequencing: application to the leopard cat ( Prionailurus bengalensis ) in Pakistan - WASIM SHEHZAD; TIAYYBA RIAZ; MUHAMMAD A. NAWAZ; CHRISTIAN MIQUEL; CAROLE POILLOT; SAFDAR A. SHAH; FRANÇOIS POMPANON; ERIC COISSAC; PIERRE TABERLET (Molecular Ecology, 2012)
Diet analysis is a prerequisite to fully understand the biology of a species and the functioning of ecosystems. For carnivores, traditional diet analyses mostly rely upon the morphological identification of undigested remains in the faeces. Here, we developed a methodology for carnivore diet analyses based on the next‐generation sequencing. We applied this approach to the analysis of the vertebrate component of leopard cat diet in two ecologically distinct regions in northern Pakistan. Despite being a relatively common species with a wide distribution in Asia, little is known about this elusive predator. We analysed a total of 38 leopard cat faeces. After a classical DNA extraction, the DNA extracts were amplified using primers for vertebrates targeting about 100 bp of the mitochondrial 12S rRNA gene, with and without a blocking oligonucleotide specific to the predator sequence. The amplification products were then sequenced on a next‐generation sequencer. We identified a total of 18 prey taxa, including eight mammals, eight birds, one amphibian and one fish. In general, our results confirmed that the leopard cat has a very eclectic diet and feeds mainly on rodents and particularly on the Muridae family. The DNA‐based approach we propose here represents a valuable complement to current conventional methods. It can be applied to other carnivore species with only a slight adjustment relating to the design of the blocking oligonucleotide. It is robust and simple to implement and allows the possibility of very large‐scale analyses.

Erratum to: Caprine pleuropneumonia in Beetal goats - Riaz Hussain; Muhammad Auon; Ahrar Khan; Muhammad Zargham Khan; Fazal Mahmood; Sajjad Ur-Rehman (Tropical Animal Health and Production, 2012)

Contagious caprine pleuropneumonia in Beetal goats - Riaz Hussain; Muhammad Auon; Ahrar Khan; Muhammad Zargham Khan; Fazal Mahmood; Sajjad Ur-Rehman (Tropical Animal Health and Production, 2012)

Effect of Zinc and Iron Fortification of the Feed on Liver and Thyroid Function in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; M. Riaz; Muhammad Arshad; Abdul Basit; Tariq Ismail (Biological Trace Element Research, 2011)

Effect of Mineral Fortification on Plasma Biochemical Profile in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; Munammad Tauseef Sultan; Muhammad Riaz; Anwaar Ahmed (Biological Trace Element Research, 2011)

Photostability and Interaction of Ascorbic Acid in Cream Formulations - Iqbal Ahmad; Muhammad Ali Sheraz; Sofia Ahmed; Riaz Hussain Shaikh; Faiyaz H. M. Vaid; Saif ur Rehman Khattak; Shakeel A. Ansari (AAPS PharmSciTech, 2011)

A molecular evaluation of dengue virus pathogenesis and its latest vaccine strategies - Muhammad Faheem; Ummar Raheel; Muhammad Nasir Riaz; Naghmana Kanwal; Farakh Javed; Najam us Sahar Sadaf Zaidi; Ishtiaq Qadri (Molecular Biology Reports, 2011)

Pathological and genotoxic effects of atrazine in male Japanese quail (Coturnix japonica) - Riaz Hussain; Fazal Mahmood; Muhammad Zargham Khan; Ahrar Khan; Faqir Muhammad (Ecotoxicology, 2011)

Determination of Pesticide Residues in Rice Grain by Solvent Extraction, Column Cleanup, and Gas Chromatography-Electron Capture Detection - Riaz Uddin; Sajid Iqbal; Muhammad Farhanullah Khan; Zahida Parveen; Mubarik Ahmed; Muhammad Abbas (Bulletin of Environmental Contamination and Toxicology, 2011)

Elaeagnoside, chymotrypsin inhibiting steroidal glucoside from Elaeagnus orientalis - Muhammad Ayaz; Muhammad Riaz; Abdul Malik; Ejaz Ahmad; Itrat Fatima; Muhammad Arif Lodhi; Muhammad Iqbal Chaudhary (Natural Product Research, 2009)

Stability of Vitamins during Extrusion - Mian N. Riaz; Muhammad Asif; Rashida Ali (Critical Reviews in Food Science and Nutrition, 2009)

Chymotrypsin inhibitory constituents from Haloxylon recurvum - Ejaz Ahmed; Abdul Malik; Nighat Afza; Naheed Riaz; Itrat Anis; Ahsan Sharif; Sadia Farheen; Muhammad Arif Lodhi; Muhammad Iqbal Choudhary (Natural Product Research, 2007)